Potassium iodide enhances riboflavin-mediated photodynamic inactivation of Escherichia coli and Penicillium expansum for fresh-cut fruit preservation - Jiayue Jin; Zheng Wu; Yibo Liu; Yile Zhao; Jingying Shi; Da Wang; Xiangzheng Yang; Di Wu; Kunsong Chen (Postharvest Biology and Technology, 2026)

Experimental and analytical investigations of composite girders with CSW-CFST chord-UHPC slab under impact loading - Wei Xian; Shuang-Shuang Li; Wen-Da Wang; Yan-Li Shi; Wei-Hong Wu; Wensu Chen (Engineering Structures, 2026)

Lateral impact performance of concrete-encased concrete-filled steel tubular (CECFST) members after exposure to fire: Tests and analysis - Yuan Zheng; Wen-Da Wang; Sun-Hang Ji; Yan-Li Shi; Wei Xian; Rui Wang (Engineering Structures, 2026)

Methylene blue-functionalized blue/red dual-emissive carbon dots for ratiometric fluorescence detection of sunset yellow in food - Sihao Wang; Yifan Zhang; Dejin Lin; Jingqi Wang; Yihao Zhang; Siting Peng; Junyuan Shi; Siqi Xu; Da Chen (Analytica Chimica Acta, 2026)

Assessing the nutritional reversibility of high-carbohydrate-induced muscle quality deterioration in male Pelodiscus sinensis: A two-phase dietary switch study - Xiangce Li; Da Yue; Xueying Shi; Xinxin Zhang; Yongqin Tu; Xiaolin Dong; Peiyu Zhang; Haiyan Liu (Aquaculture, 2026)

Natural H2 potential in mature volcanic passive margins: A Pelotas Basin overview - Henrique Serratt; Adalene Moreira Silva; Laurent Geoffroy; Tiago Girelli; Matheus Fernandes da Cruz; Peng Peng; Wenbei Shi; Bruno Conti; Marcos Antonio Klunk; Farid Chemale (Journal of South American Earth Sciences, 2026)

Dual built-in electric fields in donor–acceptor engineered poly(triazine imide) for selective lignin Cα–Cβ bond cleavage to aromatic monomers - Xudong Guo; Huifang Ma; Youheng Zhao; Hao Nie; Liping Zhao; Shuangzhen Guo; Linglong Shi; Da Li; Jianjie Wang (Journal of Environmental Chemical Engineering, 2026)

Thermodynamic compatibility and conformational adaptability enable the matrix-adaptive protection of glycated pea protein isolate-curcumin nanoparticles in frying oils - Zhi-feng Tan; Cong Sun; Shi-hui Zhao; Zhen-wen Shao; Da-yong Zhou; Liang Song (Food Chemistry, 2026)

An orally administered colon-targeted mesalamine nano-prodrug for enhanced therapy and prevention of inflammatory bowel disease - Xiao-Han Tian; Da-Yuan Wang; Si-Yu Li; Shuna Cao; Feng Liu; Mingqing Zhang; Linqi Shi (Chemical Engineering Journal, 2026)

Dynamic modeling and numerical simulation of dense particle multiphase flows in resonant acoustic mixing - Jingming Zhang; Mingming Shi; Bao Rong; Gouping Wang; Da Li; Xiaoting Rui (Chemical Engineering Journal, 2026)

Mechanistic insights into the adsorption and separation of nonpolar molecules on delocalization porous carbon: Dispersion interactions enhanced by multiple bonds - Peixin Wang; Jingxu Tian; Da Wei; Yue Sun; Bo Liu; Wenji Pi; Jun Ma; Yunfeng Zhang; Hongyu Chen; Rui Shi; Yang Guo; Xiang Xu; et al. (Chemical Engineering Journal, 2026)

Tough lean-water hydrogel electrolyte with enhanced ionic conductivity for high-performance aqueous zinc-ion batteries - Liang Chen; Julu Qiu; Shuyi Guo; Da Shi; Qingrong Wang; Yan Wang; Jialu Chen; Liubin Zhao; Ping Rao; Wenshan Ren (Chemical Engineering Journal, 2026)

Mechanochemical Fabrication of UiO-66-Supported Nilotinib Polymorphs for Drug Delivery - Junjie Peng; Youqin Wang; Jianghao Yuan; Mingkang Xu; Da Wu; Bokai Kong; Zhijie Zhang; Xiangjun Shi; Weike Su (Journal of Pharmaceutical Innovation, 2026)

Dynamic responses of CFST column to steel beam joints subjected to impact loading - Wei Xian; Wensu Chen; Yan-Li Shi; Wen-Da Wang; Long Zheng; Jun-Liang Yao (Engineering Structures, 2026)

Integrated geophysical investigation of a contaminated abandoned industrial site validated by borehole sample analysis: A case study in northeastern Shanghai, China - Shi-Jin Feng; Jin-Hui Shu; Xiao-Lei Zhang; Qi-Teng Zheng; Zhen-Xing Sun; Wen-Da Wang (Engineering Geology, 2026)

Enhancing source-level DC component of AC triboelectric nanogenerator via mirror asymmetry mechanism - Zhaojuan Shi; Sheng Zhang; Menghe Gao; Wenxuan Li; Yinxi Da; Zeming Guo; Jianjun Li; Qiang Tang; Cheng Xu (Chemical Engineering Journal, 2026)

Hypertrophic cardiomyopathy-linked Tnnc1 variants are associated with distinct myopathic changes in slow skeletal muscle of mice - Sonu Patel; Gabriel Leite da Silva Santos; Jaelynn Florence; Aida Rahimi Kahmini; Yun Shi; Michelle Rodriguez Garcia; Bradley S. Gordon; P. Bryant Chase; Christopher Solís; Orlando Laitano; J. Renato Pinto; Michelle S. Parvatiyar (Journal of Muscle Research and Cell Motility, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Trichodermine A, a new polyketide from the endophytic Trichoderma sp. MH550506.1 associated with Gardenia jasminoides - Yan-Li Zhang; Jie-Zhen Shi; Tong-De Zhao; Han-Wei Ruan; Ju-Cheng Zhang; Jin-Hua Yu; Da-Mei Wang; Li-Feng Wang; Liang Deng; Dong Gan; Zhong-Tao Ding (Phytochemistry Letters, 2026)

Isolation, structural elucidation, and activities evaluation of proaporphine alkaloids from Thalictrum baicalense - Meng-Yue Yang; Jing-Jing Xue; Zhao-Jing Chen; Xiao-Peng Guo; Shi-Meng Qin; Han-Gao Yang; Fang-Shen Liu; Zhan-Lin Li; Da-Hong Li; Ya-Ting Sun; Hui-Ming Hua (Phytochemistry, 2026)

Climate change during the early Middle Jurassic: Evidence from coal-bearing strata of the Ordos Basin - Nian-De Shang; Jing-Jing Liu; Shi-Feng Dai; Ian T. Graham; Qiu-Chan Han; Rong-Kun Jia; Jia-Wei Feng; Meng-Da Yao; Yan Wang (Palaeoworld, 2026)

Mechanochemical fabrication of Se-doped poly(triazine imide) with donor–acceptor motifs for photocatalytic cleavage of C–C bonds in lignin - Xudong Guo; Shuangzhen Guo; Linglong Shi; Da Li; Hao Nie; Jianjie Wang; Liping Zhao; Yihan Sun; Sitong Wu; Zeyun Hao (Bioresource Technology, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

A previously undescribed 3,4-secodammarane derivative from Ailanthus altissima - Yu-Sha Shi; Li-Lian Zhao; Li Huang; Su Hu; De-Feng Peng; Zhuo-Hong Li; Yun Deng; Da-Le Guo (Natural Product Research, 2026)

Study on the relationship between surface deformation and internal fracturing of tunnel surrounding rock under uniaxial loading with multiple blasting disturbances - Tian-Xiao Chen; Shi-Da Xu; Ben-Guo He; Yuan-Hui Li; Jian-Yu Peng (Tunnelling and Underground Space Technology, 2026)

Optimizing multidimensional land use for flood regulation supply-demand matching: Evidence from a GWRF-SHAP model - Weihao Shi; Jian Tian; Jiahao Zhang; Aihemaiti Namaiti; Weijie He; Da Zhang; Jian Zeng (Journal of Environmental Management, 2026)

Ultrasound-driven structural and functional modifications of grape seed protein revealed by power- and duration-dependent experiments - Ying-Yang Liu; Da-Rui Tang; Shi-Ling Wang; Wei-Wei Li; Jun-Wei Xu; Lian-Bing Lin; Yu-Hang Jiang; Qi-Lin Zhang (Food Hydrocolloids, 2026)

Research Progress on the Synthesis, Signal Transduction, and Functions of Plant Hormones in Potassium Deficiency Responses - Liu-Yang Wu; Shuai-Kun Wang; Hai-Nan Liu; Mao-Song Pei; Qiao-Fang Shi; Da-Long Guo; Tong-Lu Wei (Journal of Plant Growth Regulation, 2026)

Effects of vertical stress and wetting path on undisturbed granite residual soil and slope failure mode transition - Yong-qing Chen; Zi-yu Liu; Shi-cheng Zhao; Peng Liu; Da-wei Huang; Xin Kang (Transportation Geotechnics, 2026)

Endothelial FAM171A2 is required for maintaining autophagy flux and blood–brain barrier integrity - Si-Da Han; Ning Ding; Jia-hui Huang; Yi-Wei Feng; Kai-Min Wu; Shi-Dong Chen; Qiang Dong; Mei Cui; Ting-ting Wang; Peng Yuan; Jin-Tai Yu (Science Bulletin, 2026)

New grylloblattid insect from the Lower Triassic Kayitou Formation of Yunnan Province, Southwest China - Shi-Xue Hu; Jin-Yuan Huang; Qi-Yue Zhang; Chang-Yong Zhou; Wen Wen; Xiao Min; Da-Ran Zheng; Qian-Qi Zhang (Palaeoworld, 2026)

The oldest rock in the Eurasian continent was reworked from Hadean protocrust - Xiao-Fei Qiu; Da Wang; Xi-Run Tong; Shi-Wen Xie; Nian-Wen Wu; Fei Liu; Yu-Sheng Wan (Gondwana Research, 2026)

Preparation of polybutylene adipate terephthalate-based degradable nanofibrous membranes loaded with metal-organic frameworks for linear and sustained release of thymol via microfluidic blown spinning for fruit preservation - Feifei Wang; Xiaohong Guo; Wenjing Shi; Xiangju Feng; Yongrui Ti; Xiangzheng Yang; Da Wang; Jiangkuo Li; Zhiqiang Wang; Zhengan Yang; Di Wu; Kunsong Chen (Food Packaging and Shelf Life, 2026)

Portable smartphone-assisted fluorescence platform based on dual-excitation nitrogen-doped carbon dots for simultaneous detection of chlorogenic acid and tinidazole - Junyuan Shi; Zihang Yin; Dejin Lin; Dingfeng Wang; Siting Peng; Wendi Xiao; Houwen Hu; Jiong Cheng; Da Chen (Analytica Chimica Acta, 2026)

Dynamics and drivers of last-resort antibiotic resistance genes during pilot-scale aerobic fermentation of municipal sludge and subsequent bok choy pot trials - Li-Tao Zhou; Da-Hai He; Jiang Li; Ruo-Xue He; Shi-Jin Ma; Guang-Yu Gong; Xiao-Shuang Zou; Sen Li; You-Fei Zhou; Wei-Jie Hu (Journal of Hazardous Materials, 2026)

Bioactive edestin peptides from hemp (Cannabis sativa L.) seeds improve exercise performance under hypobaric hypoxia - Rui Zhang; Jie Liu; Liang-Liang Chen; Jia-Qi Liu; Xiao-Qian Jin; Zi-Xian Fu; Jun-Bin Xiong; Bin Jia; Jun-Ling Shi; Da-Chuan Yin (Food Research International, 2026)

The VvSAP8-VvHAK5 module from grape confers dual tolerance to potassium deficiency and salt stress by regulating potassium transport - Tong-Lu Wei; Ze-Hang Wang; Liu-Yang Wu; Shuai-Kun Wang; Qiao-Fang Shi; Mao-Song Pei; Hai-Nan Liu; Da-Long Guo (Plant Cell Reports, 2026)

Biogeographic Barriers and Historic Climate Shape the Genetic Structure and Demography of the Freshwater Crab (Brachyura, Potamidae) in Continental‐Island Systems - Ruxiao Wang; Meijun Liu; Ruyi Jin; Boyang Shi; Hongying Sun; Da Pan (Zoologica Scripta, 2026)
Island biogeography provides a crucial framework for interpreting global biodiversity patterns; however, the distinctive dynamics of continental islands remain underexplored relative to those of volcanic oceanic islands. This knowledge gap obscures our understanding of species dispersal and evolution, particularly on small continental islands whose connectivity has been modulated by Quaternary sea‐level oscillations. Here, we integrate double‐digest restriction‐site‐associated DNA (ddRAD) sequencing with mitochondrial COI and 16S rRNA data to investigate the phylogeography, population structure, demographic history and ecological niche of the narrowly distributed freshwater crab Nanhaipotamon nanriense inhabiting mainland and nearby islands in southeastern China. Our analyses revealed strong genetic differentiation, highlighting a deeply divergent island lineage isolated by a narrow marine channel and an inland lineage isolated by the Minjiang River. Demographic reconstructions indicated significant population expansions during lower sea level in the Pleistocene, followed by population contractions correlated strongly with post‐glacial sea level rise in the Holocene. By synthesising genomic, demographic and ecological evidence, our study demonstrates how marine inundation, riverine barriers and glacio‐eustatic cycles jointly shape the genetic and distributional patterns of continental island freshwater species and also provide critical insights for conservation strategies.

Bio-inspired White Tablet Coating Film Without Titanium Dioxide - Yutong Tian; Shihao Song; Yaojie Shi; Li Yuan; Jiaqi Yan; Da Wang; Luping Sha; Li Yang (Pharmaceutical Research, 2026)

Engineering acid-base active sites on an N-doped biochar catalyst for microwave-assisted biodiesel production from waste cooking oil - Supongsenla Ao; Shiva Prasad Gouda; Da Shi; Jasha Momo H. Anal; Umer Rashid; Balkis Hazmi; Arthur J. Ragauskas; Samuel Lalthazuala Rokhum (Process Safety and Environmental Protection, 2026)

Structurally diverse sesquiterpenoids from the fruits of Magnolia grandiflora Linn. and their cytotoxic activities - Qiu-Ye Zhao; Jin-Da Li; Shi-Huan Yin; Zhen-Quan Li; Hui-Ling Zhou; Jia-Qing Feng; Wei-Yang Feng; Xing-De Wu; Lin-Fen Ding (Phytochemistry, 2026)

Distinct profiles and elevated exposure to liquid crystal monomers in urban areas: Insights from indoor dust across China - Ye-Yang Hou; Da-Jian Li; Shi-Yang Liu; Peng-Ran Guo; Liang-Ying Liu (Environmental Research, 2026)

Physics-informed stacking ensemble machine learning for fatigue life prediction of stud connectors in steel-concrete composite structures - Benkun Tan; Fanghuai Chen; Da Wang; Jialin Shi; Chengong Zhao (Engineering Structures, 2026)

Novel kinked connection component (KCC) for enhanced progressive collapse performance in CFST column–steel beam joints - Long Zheng; Yu-Chen Zhang; Yan-Li Shi; Wen-Da Wang; Yin-Quan Yu (Engineering Structures, 2026)

Genetic improvement of nitrogen- and phosphorus-use efficiency in crops: Old goals with new aspirations - Wei Wang; Da Chen; Huwei Sun; Surya Kant; John P. Hammond; Lei Shi; Chengcai Chu (Molecular Plant, 2026)

Advances in understanding the MicroRNA-transcription factor regulatory network governing terpenoid biosynthesis in medicinal plants - Jingyi Xu; Yue Shi; Xiaoqian Xie; Yueting Xie; Jing Tian; Yue Ren; Yuan Li; Da Li; Chunmei Yang; Qile Zhou; Jinhui Man; Hui Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Zedoarondiol inhibits monocyte adhesion and expression of VCAM and ICAM in endothelial cells induced by oxidative stress - Bei-li Xie; Yu-long Bie; Bo-ce Song; Ming-wang Liu; Lin Yang; Jiangang Liu; Da-Zhuo Shi; Fu-Hai Zhao (Natural Product Research, 2026)

TMEM158-mediated TGF-β signaling pathway modulates the sensitivity of TP53-deficient osteosarcoma to USP14 inhibitors - Zi-Yu Chen; Miersalijiang Yasen; Song-Yao Jiang; Zi-Yi Ye; Qin-Xin Yang; Cui-Ni Lu; Yi Shi; Xin-Yun Liu; Ting-Ting Du; Xiao-Mei Tang; Da Fu; Yu-Shui Ma; et al. (Molecular and Cellular Biochemistry, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

The first cranium of Postschizotherium (Pliohyracidae, Hyracoidea) from the Lower Pleistocene of China - Lu-Da Xing; Xiao-Bing Wang; Martin Pickford; Yan-Jie Chen; Jiao Ma; Shu-Qiong Wang; Yi-Yang Liu; Shi-Qi Wang (Palaeoworld, 2026)

Acrylonitrile exposure incurs lung function decline: Insights from lifestyle intervention and mechanistic pathway in an urban prospective cohort - Shuhui Wan; Jiahao Song; Yongfang Zhang; Yueru Yang; Da Shi; Xiaojie You; Ruyi Liang; Le Hong; Qing Liu; Zhiying Huo; Wei Liu; Wendi Shi; et al. (Environmental Research, 2026)

Decreasing internal reorganization energy via inactivating iodine defects to optimize Marcus-Gerischer charge mobility for high-performance carbon-based perovskite solar cells - Cai-Xia Li; Wen-Wu Liu; Shi-Ji Da; Ling-Bin Kong (Chemical Engineering Journal, 2026)

NeuProIO: A dual-action solid drug nanoparticle topical formulation for simultaneous intraocular pressure reduction and neuroprotection for glaucoma - Lei Xu; Mu Li; Lin Qi; Tzu-Chen Wang; Dong Liu; Vimalin Jeyalatha Mani; Hsin-Yin Chuang; Qingbo Yang; Ruipu Mu; Samira Mahdi; Da Huang; Honglan Shi; et al. (Chemical Engineering Journal, 2026)

Catalytic conversion of fatty acid methyl esters to biofuels under mild reaction conditions - Xiaolong Yan; Lei Wang; Weimin Da; Yawen Shi; Zhaowei Tian; Zhitong Qian; Yu Sun; Xu Zhao; Xin Zhang; Weiming Zhai; Feng Liu; Yusen Yang; et al. (Chemical Engineering Journal, 2026)

Influence of pacific decadal oscillation on decadal precipitation variation over the Yellow River Basin - Tingting Ma; Xiaodan Guan; Xiang Zuo; Shi Jin; Pengbo Da (Atmospheric Research, 2026)

A new polyketide from Penicillium sp. HK-G2 and its inhibitory activity against α-glucosidase - Jie Zhen Shi; Yan-Li Zhang; Jin Hua Yu; Da-Mei Wang; Dong Gan; Zhong-Tao Ding (Natural Product Research, 2025)

Spermidine enhances cold tolerance in tomato fruit by boosting antioxidant and energy metabolism synergy - Jian-Lin He; Shi-Yin Xie; Xiao-Dan Zhao; Da-Qi Fu (Food Research International, 2025)

Glued laminated bamboo roof trusses with stainless-steel tubular rivet connections: Connection and global behavior - Guoshan Lu; Hanlin Wei; Da Shi; Zhi Li; Beibei Xiong; Tommaso Albanesi; Carlotta Contiguglia; Cristoforo Demartino (Engineering Structures, 2025)

Organically-coordinated Cu(II) mediated AOPs: A comparative study on different peroxides - Mengyao Shi; Qiang Yin; Da Wang; Chengcheng Tian; Lei Zhou (Chemical Engineering Journal, 2025)

Dynamic 3-hydroxyflavone-modified D-alanine nanoparticles for metabolic-incorporation in anaerobic, pathogenic biofilms generating CO in infected periodontal pockets - Da-Yuan Wang; Jing Li; Xiao-Han Tian; Siyu Zhang; Yao Chen; Feihe Ma; Henk.J. Busscher; Jing Shen; Linqi Shi (Chemical Engineering Journal, 2025)

Corrigendum to “Evaluation of bacteriostatic and antioxidant screening of secondary metabolites of endophytic fungi in Lanzhou lily” [Bioresour. Technol. Rep. 32 (2025) 102380] - Xinlan Wang; Bolu Sun; Ying Lv; Miao Zhou; Xuanxiu Da; Jiali Kang; Haiying He; Chenyu Qin; Quhuan Ma; Hongxia Shi; Lin Yang; Xiaofeng Shi (Bioresource Technology Reports, 2025)

Evaluation of bacteriostatic and antioxidant screening of secondary metabolites of endophytic fungi in Lanzhou lily - Xinlan Wang; Bolu Sun; Ying Lv; Miao Zhou; Xuanxiu Da; Jiali Kang; Haiying He; Chenyu Qin; Quhuan Ma; Hongxia Shi; Lin Yang; Xiaofeng Shi (Bioresource Technology Reports, 2025)

Voltage-Gated sodium channel Nav1.6 mediates glioblastoma proliferation and migration via Na+/H+ Exchanger-1 and inhibits apoptosis through ERK-AKT pathway - Samed Ahmed Alezzi Alameri; Yue Kong; Qing-Da Shi; Yue-Lin Huang; Ao-Ran Sui; Dan-Dan Zhu; Ying-Zi Wang; Wang Miao; Shao Li; Guang Yang (Molecular Biology Reports, 2025)

Low self-fertilization rate and putative self-incompatibility in Codonopsis pilosula (Campanulaceae) - Hui Zhang; Shaoming Shi; Lujie Yang; Fan Zhao; Zhiqi Wang; Ying Zhang; Jing Fang; Yujie Zhang; Lingling Da (Genetic Resources and Crop Evolution, 2025)

Heterogeneous microcosm mazes affect reproduction and survival in a wingless hyperparasitoid wasp - Xianhui Shi; Rieta Gols; Jetske G. de Boer; Jitske Spee; Irla Hanum; Sergio A. Pelaez-Plazas; Jocelyn da Cruz Freitas; Jeffrey A. Harvey (Animal Behaviour, 2025)

Challenges and solutions in measuring commonly used biomarkers for drug-induced liver injury in a liver-on-a-chip platform - Qiang Shi; Laura K. Schnackenberg; Lijun Ren; Katy S. Papineau; Jessica J.H. Oliphant; Mark I. Avigan; Lorna Ewart; John FK. Sauld; Emily Dai; Paul C. Brown; Karen L. Davis Bruno; Frederic Moulin; et al. (Toxicology Letters, 2025)

Advanced supramolecular food safety sensing technology: principles and applications - Hongbin Pu; Chuying Shi; Da-Wen Sun (Food Chemistry, 2025)

Experimental and analytical investigations of prefabricated RC beam to CFST column joints subjected to beam-end impact loads - Wei Xian; Zhi-Meng Wang; Wensu Chen; Yan-Li Shi; Wen-Da Wang (Engineering Structures, 2025)

Study on the role and function of RRS1 in cutaneous squamous cell carcinoma - Zhan-Yan Pan; Zhi-Nan Shi; Qiong Wu; Ting-Ting Hu; Xiao-Hui Mo; Da-Ke Dong; Qiang Ju (Tissue and Cell, 2025)

OsSPT38 encodes a novel SUMO E3 ligase that improves rice stress resilience and grain yield - Zi-Sheng Zhang; Zheng-Yi Zhang; Jin-Qiu Xia; Si-Yan Chen; Liang-Qi Sun; Jie Wu; Da-Yu He; Jing-Xian Wang; Qin-Yu Liang; Lei Wang; Ke Ruan; Tian Sang; et al. (Molecular Plant, 2025)

Unveiling the key drivers and formation pathways for secondary organic aerosols in an eastern China megacity - Fei Zhang; Jiasi Shen; Da Xu; Jiandong Shen; Yiming Qin; Ruifang Shi; Jing Wei; Zhengning Xu; Xiangyu Pei; Qian Tang; Hui Chen; Bingye Xu; et al. (Journal of Hazardous Materials, 2025)

Molecular and microscale–level insights into the potential mobilization of toxic elements in Pb/Zn smelting contaminated soils under freeze–thaw cycles - Yu–Xiang Shi; Da–Mao Xu; Dong–Sheng Dai; Ze–Lin Xu; Bai–Hong An (Journal of Hazardous Materials, 2025)

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

Smart construction of 8N-CuO for efficient peroxymonosulfate (PMS) activation: The synergistic effect of 8N-CuO-induced non-radical/radical pathways - Linglong Shi; Da Li; Shuangzhen Guo; Lihong Zhang; Jiaxin Bai; Mengqi Li; Sizhe Peng; Meiqi He; Yan Li; Yu Liu (Journal of Environmental Chemical Engineering, 2025)

Associations of perchlorate, nitrate, and thiocyanate with oxidative stress, inflammatory, and lung diseases: Evidence from a nationally representative population-based study - Wei Liu; Shuting Cao; You Guo; Yanfang Gao; Xiaokang Zhang; Da Shi; Lei Huang (Environmental Pollution, 2025)

Leveraging reinforcement learning for optimal control of chiller plant with complex hydraulic and thermodynamic characteristics - Xiao Wang; Huiming Xu; Cheng Fan; Shengyu Tan; Xuyuan Kang; Yang Shi; Da Yan (Energy and Buildings, 2025)

Mechanical response of tunnel surrounding rock under blasting disturbance with different stress conditions based on acoustic emission and digital image correlation - Tian-xiao Chen; Shi-da Xu; Ben-guo He; Yuan-hui Li; Han Lei (Engineering Geology, 2025)

Single Iron Atom with Porphyrin Coordination Environment Decorated Graphited Carbon Nitride for Photocatalytic Selective Semi-Dehydrogenation of THIQ - Jihui Wang; Haoyu Shi; Chengjia Qian; Shuyan Zhang; Kejian Ding; Songmei Wu; Da Wang; Jian Liu; Yu Yu (Chemical Engineering Journal, 2025)

Multidimensional mechanism investigation on improving the pretreatment performance and enzymatic saccharification of bamboo with choline chloride-based deep eutectic solvents - Yu Sheng; Yao-yao Jin; Hai-yan Yang; Zheng-jun Shi; Chun Shi; Da-wei Wang; Tao-hong Li; Jing Yang (Chemical Engineering Journal, 2025)

Insights Into the Separate and Joint Effects of Cadmium and Cesium on the Risk of Circadian Syndrome and the Underlying Mechanism: An Integrated Epidemiological and Network Toxicological Study - Zhiying Huo; Wei Liu; Qiang Sun; Jiahao Song; Shuhui Wan; Wendi Shi; Yueru Yang; Le Hong; Qing Liu; Yongfang Zhang; Da Shi; Weihong Chen; et al. (Biological Trace Element Research, 2025)

Volatile organic compounds exposure, biological ageing, and increased sarcopenia risk: Association, interaction, and mechanistic exploration - Le Hong; Qing Liu; Wei Liu; Jiahao Song; Shuhui Wan; Zhiying Huo; Yongfang Zhang; Da Shi; Ruyi Liang; Bingdong Chen; Yani Xiong; Feifei Wang; et al. (Journal of Hazardous Materials, 2025)

Screening of biocontrol agents against lily bulb rot caused by F. oxysporum and research on their fermentation process - Bolu Sun; Xinlan Wang; Ying Lv; Xuanxiu Da; Miao Zhou; Jiali Kang; Haiying He; Chenyu Qin; Xiangdong Wang; Lin Yang; Quhuan Ma; Hongxia Shi; et al. (Bioresource Technology Reports, 2025)

Efficient and selective gold recovery from practical e-waste and electroplating wastewater using protein crystals - Xiao-Qian Jin; Jia-Lei Li; Chen-Yuan Li; Liang-Liang Chen; Xue-Ting Wang; Wen-Pu Shi; Jun-Bin Xiong; Rui Zhang; Wei-Hong Guo; Da-Chuan Yin (Resources, Conservation and Recycling, 2025)

Leakage detection and localization of large diam water pipeline based on multi-source geophysical data analysis - Shi-Jin Feng; Wen-Da Wang; Xiao-Lei Zhang; Hang Chen; Qi-Teng Zheng; Yong Zhao (Engineering Geology, 2025)

Calcium oxide modification of phosphorus migration pathways during hydrogen reduction of high-phosphorus limonite - Lian-da Zhao; Mei-lin Shi; Xing-jian Deng; Jing-song Wang; Guang Wang; Qing-guo Xue; Hai-bin Zuo; Xue-feng She (Process Safety and Environmental Protection, 2025)

Dual structure Brønsted sites activated carbon beads solid acid enhances the highly efficient synthesis of HMF: From batch to continuous - Wei-Yao Yang; Meng Wen; Hong-Da Zhang; Ya-Qiao Tian; Shi-Chao Su; Yu Lang; Zhi-Ping Zhao; Le Sang (Chemical Engineering Journal, 2025)

Visual-language reasoning segmentation (LARSE) of function-level building footprint across Yangtze River Economic Belt of China - Da He; Xiaoping Liu; Qian Shi; Yue Zheng (Sustainable Cities and Society, 2025)

Identification of novel sulfur-containing petroporphyrins in a natural bitumen: Potential biomarkers for aerobic organisms - Fang Zheng; Weisheng Yang; Yanbin Wang; Mi An; Da Huo; Chunyan Wang; Qing Cao; Jing He; Quan Shi; Yongge Sun (Organic Geochemistry, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Dynamic stiffness of full-scale damaged polyester mooring ropes - Yushun Lian; Yongyue Xie; Jinhai Zheng; Wenxing Chen; Da Li; Shichang Chen; Jisheng Zhang; Xiang Wu; Jiaoxue Shi; Solomon C. Yim (Ocean Engineering, 2025)

Impact load identification of ship panels under tire drop action based on the data-driven regression with regularization - Gui-jie Shi; De-yu Wang; Da-wei Gao; Qiang Li (Ocean Engineering, 2025)

Associations of polycyclic aromatic hydrocarbons exposure with serum uric acid and hyperuricemia in US adults: The role of systemic inflammation - Yang Liu; Xuejie Ding; Linling Yu; Da Shi; Ruyi Liang; Wei Liu; Xuezan Huang; Xiuyu Cao; Min Zhou; Weihong Chen (Journal of Environmental Sciences, 2025)

Simultaneous electricity production and pollutant removal via photocatalytic fuel cell utilizing Bi2O3/TiO2 porous nanotubes decorated by g-C3N4 - Sheng-Zhe Zhao; Rui-Dong Shi; Guo-Tao Xiang; Yong-Da Hu; Jin-Ju Chen (Fuel, 2025)

Recyclable and reused peroxymalic acid pretreatment for enhancing enzymatic saccharification and ethanol production of bamboo residues - Zhen-tai Wei; Chen-kai Qiu; Hai-yan Yang; Zheng-jun Shi; Chun Shi; Da-wei Wang; Jing Yang (Chemical Engineering Journal, 2025)

Comparative efficacy of anaerobic digestion systems in removing antimicrobial resistance genes from swine wastewater - Da Sun; Xiaomin Shi; Yingbo Shen; Ying Liu; Sunlin Luo; Yongpeng Jin; Weishuai Zhai; Lu Liu; Zhaoju Deng; Chengtao Sun; Dejun Liu; Xin Yang; et al. (Journal of Hazardous Materials, 2025)

Numerical analysis on fire behaviour of concrete-filled steel tubular columns after lateral impact - Sun-Hang Ji; Wen-Da Wang; Yan-Li Shi; Jing-Xuan Wang (Engineering Structures, 2025)

Functional microorganisms in hydrogen production: Mechanisms and applications - Yonghong Fan; Feiran Zhang; Kun He; Dan Yu; Haoming Chen; Da Tian; Yixiao Shi; Zhen Li; Xiaomei Wang (Bioresource Technology, 2025)

Paleoclimate Fluctuations Facilitate the Biogeographical History of Endemic Species of Freshwater Crabs in China via Cycles of Introgressive Hybridisation and Habitat Isolation - Boyang Shi; Ruxiao Wang; Danhong Song; Juanjuan Xu; Lin Zhu; Yufang Sun; Rui Hu; Neil Cumberlidge; Da Pan; Hongying Sun (Journal of Biogeography, 2025)
Aim The impact of Pleistocene climate fluctuations on the biogeographical history of aquatic species has been a topic of enduring debate. This issue poses particular challenges for parapatric closely related species, especially those situated in transition zones where species assemblages occur between distinct zoogeographic boundaries. Location Eastern China. Taxon Five closely related Sinopotamon species and subspecies, S. shensiense , S. honanense , S. y. yangtsekiense , S. y. shanxianense , and S. y. tongbaiense . Methods These parapatric Sinopotamon species and subspecies, distributed along the boundary between the Palaearctic and Oriental realms in eastern China, offer an ideal model for addressing these challenges. We explored the biogeographic history of these species by conducting a comparative phylogeographic analysis using nine microsatellite loci and two mitochondrial DNA sequences, combined with morphological variation and fine‐tuned ecological niche modelling. Results Our phylogeographic analyses consistently revealed two well‐supported clades: clade A, for S. y. yangtsekiense , and clade B, which includes other species showing polyphyletic patterning and significant gene introgression. The Nanyang Basin and surrounding mountains regions (NBSM) was identified as a critical shared refuge and hybrid zone, facilitating interspecific introgression through at least two putative hybridisation events. During the Late Pleistocene glacial cycles, introgressive hybridisation of these species occurred in the NBSM, followed by rapid expansion and colonisation of heterogenous habitats during interglacial cycles, with dispersal corridors largely aligning with the local river system. In particular, the diffusion corridor of S. honanense significantly disrupted the continuous distribution of S. y. shanxianense and S. y. tongbaiense , indicating that S. honanense has replaced S. y. shanxianense and S. y. tongbaiense in the NYSM and caused a disruption in its distribution. Main Conclusions The biogeographic histories of the species in clade B are consistent with a mixing–isolation–mixing model, which suggests that populations experienced repeated introgressive hybridisation during glacial periods and regional habitat isolation during interglacial periods. Our findings represent a classic case of fine tracking biogeographical scenarios in parapatric species and provide unprecedented insights into the evolutionary radiation of the freshwater fauna that occupies zoogeographic boundaries.

Potential influence mechanism of mineral–organic matter (OM) interactions on the mobility of toxic elements in Pb/Zn smelter contaminated soils - Da–Mao Xu; Xiong–Chao Wen; Dong–Sheng Dai; Yu–Xiang Shi; Shao–Jun Jiang; Wei–Wei Chi; Yi–Kai Liu; Lai Zhou; Xue–Qiang Zhu (Journal of Hazardous Materials, 2025)

Temporal and spatial changes of glacial lakes in the central Himalayas and their response to climate change based on multi-source remote sensing data - Xiaoqiang Cheng; Donghui Shangguan; Chengsheng Yang; Wangping Li; Zhaoye Zhou; Xiaojie Liu; Da Li; Xiuxia Zhang; Huilan Ding; Zewei Liu; Yi Yu; Xiaoxian Wang; et al. (Global and Planetary Change, 2025)

Experimental analysis and optimization of the variable valve timing on attaining high efficiency with low NOx emission of a direct-injected hydrogen engine - Feng-yu Lai; Bai-gang Sun; Shi-wei Zhang; Kang-da Wang; Qing-he Luo; Ling-zhi Bao; Felix Leach (Fuel, 2025)

Harnessing the polysaccharide production potential to optimize and expand the application of probiotics - Dong-Xu Ma; Hui-Juan Cheng; Hui Zhang; Shuo Wang; Xiao-Tao Shi; Xin Wang; Da-Chun Gong (Carbohydrate Polymers, 2025)

Improved free iodine capture by light-driven carbon-halogen bond cleavage in perovskite solar cells with dynamic self-healing ability - Cai-Xia Li; Wen-Wu Liu; Shi-Ji Da; Ling-Bin Kong (Chemical Engineering Journal, 2025)

Phylogenomic analysis of brachyuran crabs using transcriptome data reveals possible sources of conflicting phylogenetic relationships within the group - Da Pan; Yunlong Sun; Boyang Shi; Ruxiao Wang; Peter K.L. Ng; Danièle Guinot; Neil Cumberlidge; Hongying Sun (Molecular Phylogenetics and Evolution, 2024)

Association Between Neuroinflammation and Parkinson’s Disease: A Comprehensive Mendelian Randomization Study - YiNi Wang; XinYu Shi; YaPing Yin; Fei Yang; YiNan Zhang; Xin He; Da Wen; Bai-Xiang Li; Kun Ma (Molecular Neurobiology, 2024)

In-situ generation of bifunctional reagents via Al/C microelectrolysis for efficient coagulation–Fenton oxidation treatment of leachate MBR effluent - Fuliu Yang; Yong Chen; Xiaochun Wu; Yufeng Da; Peipei Xiong; Chenxi Wu; Yue Du; Yuhang Shi; Junfeng Zhao; Yong Liu (Journal of Water Process Engineering, 2024)

Shining light on broad-spectrum responded NaYF4:Yb,Er,Tm@Bi@BiOI: Understanding the enhanced photodegradation performance of bisphenol A and mechanisms - Jinyuan Zhang; Tian Shi; Qincan Ma; Shuang Fu; Da Cai; Fuhua Gao; Xianzhong Lin; Yueli Zhang (Journal of Environmental Management, 2024)

RNA reading protein YTHDF2 mediates Benzo(k)fluoranthene induced male reproductive injury by regulating the stability of BCL2 - Ya-wen Li; Dan-dan Wang; Hong-qiang Chen; Yong Zeng; Na Wang; Yu Shi; Jiang-ying Li; Ni-ya Zhou; Da-peng Wang; Qing Chen; Xue Han; Jia Cao; et al. (Environmental Pollution, 2024)

Efficient solution-processable OLEDs near BT.2020 red standard enabled by a multiresonant emitter - Hui Wang; Ying-Chun Cheng; Xiao-Chun Fan; Dong-Yang Chen; Xin Xiong; Xiao-Yao Hao; Yi-Zhong Shi; Jia Yu; Da Huang; Jia-Xiong Chen; Kai Wang; Xiao-Hong Zhang (Science Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Experimental investigation of the matching boundary and optimization strategy of a variable geometry turbocharged direct-injected hydrogen engine - Feng-yu Lai; Bai-gang Sun; Zhi-fu Zhang; Shi-wei Zhang; Kang-da Wang; Xue-ming Ju; Qing-he Luo; Ling-zhi Bao; Felix Leach (Fuel, 2024)

Distribution characteristics of sulfonamide antibiotics between water and extracellular polymeric substances in municipal sludge - Ming Cheng; Chen Shi; Bo-Han Zhao; Tai-Yue Wang; Nan-Zhang; Ran-Bin Liu; Da-Qi Cao; Xiao-Di Hao (Environmental Research, 2024)

Modeling of glubam roof truss, parameter identification and updating based on parallel genetic algorithm - Da Shi; Giuseppe Carlo Marano; Cristoforo Demartino (Engineering Structures, 2024)

Rechargeable Self-Powered pressure sensor based on Zn-ion battery with high sensitivity and Broad-Range response - Yong-Peng Hu; Kai-Yang Liu; Ruo-Ning Bai; Da-Zhuang Liu; Wei Yu; Chui-Zhou Meng; Guo-Xian Li; Shi-Jie Guo (Chemical Engineering Journal, 2024)

Multi-dimensional signals coupling of simultaneous acquisition stripping current with laser-induced breakdown spectroscopy for accurate analysis of Cd(II) in coexisting Cu(II) - Yuan-Fan Yang; Zong-Yin Song; Zi-Hao Liu; Zhi-Wei Gao; Xin Cai; Cong-Cong Huang; Pang-Da Dai; Meng Yang; Pei-Hua Li; Shi-Hua Chen; Xing-Jiu Huang (Analytica Chimica Acta, 2024)

Exposure to ambient air pollutants during circadian syndrome and subsequent cardiovascular disease and its subtypes and death: A trajectory analysis - Wei Liu; Jiahao Song; Linling Yu; Xuefeng Lai; Da Shi; Lieyang Fan; Hao Wang; Yueru Yang; Ruyi Liang; Shuhui Wan; Yongfang Zhang; Bin Wang (Science of The Total Environment, 2024)

Fruits’ cold tolerance: a review of mechanisms and methods - Jian-Lin He; Gang-Shuai Liu; Xiao-Dan Zhao; Lan-Ting Xiang; Shi-Yin Xie; Yun-Xiang Wang; Da-Qi Fu (Postharvest Biology and Technology, 2024)

Bonding-slip behaviour of steel-concrete interfaces in CFDST members with PBL ribs - Yan-Li Shi; Jia-Xing Ren; Jia-Hao Fan; Wen-Da Wang; Hai-Cui Wang (Engineering Structures, 2024)

Efficient electrocatalytic OOH production on P–N–CuO for selective cleavage of lignin C–C bonds in the photoelectric collaborative system - Linglong Shi; Huifang Ma; Bin Shan; Da Li; Shuangzhen Guo; Yu Liu; Jianjie Wang; Weifang Dong; Mengqi Li; Shuting Gu; Weiyu Xia (Chemical Engineering Journal, 2024)

Analysis of the Relationship Between Parkinson’s Disease and Diabetic Retinopathy Based on Bioinformatics Methods - XinYu Shi; YiNi Wang; YaPing Yin; Fei Yang; YiNan Zhang; Xin He; Da Wen; Kun Ma; Bai-Xiang Li (Molecular Neurobiology, 2024)

Variation in leaf N allocation and mesophyll conductance to CO2 in four tree species under low soil P stress in subtropical China - Jingchao Tang; Baodi Sun; Ruimei Cheng; Zuomin Shi; Da Luo; Shirong Liu; Mauro Centritto (Acta Physiologiae Plantarum, 2024)

Multi-strategy synergistic scheme for progressive construction and optimization of non-covalent all-polysaccharide double-network hydrogels - Qiang Yang; Jing Guo; Sen Zhang; Shi Feng; Qiang Yao; Da Bao; Yi Xu; Fucheng Guan; Xin Zhang; Jiahao He (Chemical Engineering Journal, 2024)

Upregulation of hsa-miR-141-3p promotes uterine cervical carcinoma progression via targeting dual-specificity protein phosphatase 1 - Zi-Qian Liang; Wei Zhang; Da-Tong Zeng; Jun-Hong Chen; Jia-Yuan Luo; Lin Shi; Kang-Lai Wei; Gang Chen (Functional & Integrative Genomics, 2024)

Assessment of co-benefits from on-road vehicle electrification in Suzhou City, China - Feiyue Qian; Cui Da; Chunchen Lu; Xinyu Gu; Junjian Yang; Chaowei Shi; Zhen Feng; Yuanyuan Cheng (Urban Climate, 2024)

Cyclic behavior of laminated bio-based connections with slotted-in steel plates: Genetic algorithm, deterministic neural network-based model parameter identification, and uncertainty quantification - Da Shi; Yongjia Xu; Cristoforo Demartino; Yan Xiao; Billie F. Spencer (Engineering Structures, 2024)

An improved representative of stomatal models for predicting diurnal stomatal conductance at low irradiance and vapor pressure deficit in tropical rainforest trees - Wei Xue; Xue-min He; Quan Wang; Pei-jun Shi; Guang-hui Lv; Jian-feng Huang; Da Yang; Jiao-lin Zhang (Agricultural and Forest Meteorology, 2024)

Identification and mechanism characterization of Streptomyces griseoaurantiacus XQ-29 with biocontrol ability against pepper southern blight caused by Sclerotium rolfsii - Ze Lan Qiu; Shi Da Liu; Xiao Gang Li; Jie Zhong; Jun Zi Zhu (Pesticide Biochemistry and Physiology, 2024)

Soil water potential measurement using fiber-optic sensing technique - Jin-Jian Xu; Chao-Sheng Tang; Qing Cheng; Farshid Vahedifard; Da-Zhan Zhang; Chang Sun; Bin Shi (Journal of Hydrology, 2024)

A sharp and selective fluorescence paper-based sensor based on inner filter effect for ratiometric detection of four Sudan dyes in food matrix - Tian Shi; Jinyuan Zhang; Fuhua Gao; Da Cai; Yueli Zhang (Food Chemistry, 2024)

Effect of polyphenols on the rheology, microstructure and in vitro digestion of pea protein gels at various pH - Da Chen; Shi Stone; Jan Ilavsky; Osvaldo Campanella (Food Hydrocolloids, 2024)

Bio-based hybrid planar truss: Experimental testing, FE modeling and Bayesian model updating - Da Shi; Zhi Li; Cristoforo Demartino (Engineering Structures, 2024)

Rotavirus infection inhibits SLA-I expression on the cell surface by degrading β2 M via ERAD-proteasome pathway - Zhaoyang Jing; Ling Wu; Yudi Pan; Liaoyuan Zhang; Xin Zhang; Da Shi; Hongyan Shi; Jianfei Chen; Zhaoyang Ji; Jiyu Zhang; Tingshuai Feng; Jin Tian; et al. (Veterinary Microbiology, 2024)

An active-bending sheltered pathway based on bamboo strips for indoor temporary applications: Design and construction - Junsong Wang; Da Shi; Chenyu Zhou; Qiu Zhang; Zhi Li; Francesco Marmo; Cristoforo Demartino (Engineering Structures, 2024)

A New Method for the Correction of Spectrum Drift Caused by Temperature Changes When Using a NaI(Tl) Seawater Radioactivity Sensor - Yan Shi; Yingying Zhang; Xiandong Feng; Da Yuan; Bingwei Wu; Haijie Bi (Journal of Marine Science and Engineering, 2024)
The seawater radioactivity sensor based on the NaI(Tl) scintillation crystal detection method is prone to spectrum drift due to environment temperature changes during actual measurement, which pose difficulties in the activity analysis of seawater radionuclides. This paper adopts experiment design and analysis methods to study the relationship laws between temperature and peak position channel address and between gain and the peak position channel address. On the basis of studying and summarizing the two relationship laws of the NaI(Tl) seawater radioactivity sensor, a spectrum drift correction method combining gain adjustment and spectrum processing is proposed. Laboratory air and water environment experiments verify that the peak position channel address drift after air environment correction does not exceed ±2 channels, and after water environment correction does not exceed ±1 channel. Long-term verification experiments at the seawater work site have shown that this correction method can effectively correct the spectrum drift of the NaI(Tl) seawater radioactivity sensor and meet the requirements of long-term automatic operations at sea for the measured spectrum.

Synthesis and utilization of biomass-derived sulfonated heterogeneous catalyst-BT-SO3H for microalgal biodiesel production - Supongsenla Ao; Umer Rashid; Da Shi; Samuel Lalthazuala Rokhum; Le TG Thuy; Tahani Awad Alahmadi; Arunachalam Chinnathambi; Thangavel Mathimani (Environmental Research, 2024)

Orthogonal dynamic covalent boroxine-crosslinked poly(disulfide) networks for chemically recyclable encryption materials - Mingyu Shi; Chen-Yu Shi; Qi Zhang; Da-Hui Qu (Chemical Engineering Journal, 2024)

Iodine Acetonitrile as a Drinking Water Disinfectant Showed a Potential Toxic Effect on Organism - Ya-Ping Li; Jie-Wen Cai; Pin-Ying Su; Shi-Ming Xie; Jia-Xuan Lai; Zi-Ru Xian; Jing-Da Qiao (Water, Air, & Soil Pollution, 2024)

Ionothermal synthesis of Cs3Bi2Br9 quantum dots-decorated covalent triazine frameworks composite photocatalyst and their application in selective cleavage of C–C bonds in lignin - Linglong Shi; Huifang Ma; Liming Dong; Shuangzhen Guo; Yu Liu; Da Li; Jianjie Wang; Shunli Li (Journal of Environmental Chemical Engineering, 2024)

Inhibition of nucleotide metabolism with dual-template epitope imprinted nanoparticles for targeted HER2+ tumor therapy - Xing-Hui Ren; Lei Shi; Zi-Bo Ma; Da-Wei Wang; Xi-Wen He; Wen-You Li; Yu-Kui Zhang (Chemical Engineering Journal, 2024)

Comparative life cycle cost analysis of bio-valorized magnetite nanocatalyst for biodiesel production: Modeling, optimization, kinetics and thermodynamic study - Joseph V.L. Ruatpuia; Gopinath Halder; Da Shi; Sudipta Halder; Samuel Lalthazuala Rokhum (Bioresource Technology, 2024)

Transboundary transport of non-east and East Asian dust observed at Dunhuang, northwest China - Tian Zhou; Xiaowen Zhou; Zining Yang; Carmen Córdoba-Jabonero; Yufei Wang; Zhongwei Huang; Pengbo Da; Qiju Luo; Zhijuan Zhang; Jinsen Shi; Jianrong Bi; Hocine Alikhodja (Atmospheric Environment, 2024)

IFITM3 restricts porcine deltacoronavirus infection by targeting its Spike protein - Jianxiao Wu; Rongfeng Tang; Xiaorong Zhang; Mingzhe Gao; Longjun Guo; Liaoyuan Zhang; Da Shi; Xin Zhang; Hongyan Shi; Hongying Song; Li Feng; Jianfei Chen (Veterinary Microbiology, 2024)

Diversification of freshwater crabs on the sky islands in the Hengduan Mountains Region, China - Bo-Yang Shi; Da Pan; Kang-Qin Zhang; Tian-Yu Gu; Darren C.J. Yeo; Peter K.L. Ng; Neil Cumberlidge; Hong-Ying Sun (Molecular Phylogenetics and Evolution, 2024)

Polyamide nanofiltration membrane fabricated via a metal-chelate strategy for high-flux desalination - Baolong Mi; Da Sheng; Bin Liu; Lingjun Bu; Zhou Shi; Shiqing Zhou; Shumin Zhu (Desalination, 2024)

Sulfamic acid modified UiO-66 metal-organic framework for biodiesel production: Process optimization using response surface methodology, kinetics, and thermodynamic study - Shiva Prasad Gouda; Da Shi; Sanjay Basumatary; Hui Li; Ramón Piloto-Rodríguez; Samuel Lalthazuala Rokhum (Chemical Engineering Journal, 2024)

Biosynthesis of l-histidine from marine biomass-derived galactans in metabolically engineered Corynebacterium glutamicum - Minhye Kim; Jun Won Oh; Da Woon Jeong; Byeong-Hyeon Cho; Joonhee Chang; Xiaoyu Shi; Sung Ok Han (Bioresource Technology, 2024)

Very fine spatial resolution urban land cover mapping using an explicable sub-pixel mapping network based on learnable spatial correlation - Da He; Qian Shi; Jingqian Xue; Peter M. Atkinson; Xiaoping Liu (Remote Sensing of Environment, 2023)

Effects of genotype, environment and their interaction on protein and amino acid contents in soybeans - Da Shi; Jiayi Hang; Jason Neufeld; Shusheng Zhao; James D. House (Plant Science, 2023)

Transcriptome sequencing reveals the senescence mechanism of ethylene-insensitive cut Rhododendron flowers - Shi-da Xu; Fang Zheng; Xing-min Geng; Zhi-li Jiang; Ling-feng Mao; Jia-le Su (Postharvest Biology and Technology, 2023)

C-doped ZnO nanocomposites molecularly imprinted photoelectrochemical sensor for ultrasensitive and selective detection of oxytetracycline in milk - Huafang Zhang; Qinghong Pan; Wanying Cai; Xiaowei Shi; Da-Peng Yang; Hetong Lin; Enhui Qiu (Food Chemistry, 2023)

Synthesis of flower-shaped cyclodextrin microporous organic networks for selective recovery of acetophenone and 1-phenylethanol from petrochemical effluents - Yun-Da Yue; Yu Gao; Shi-Ya Fu; Yuan-Yuan Cui; Cheng-Xiong Yang (Chemical Engineering Journal, 2023)

Single-chemical and mixture effects of multiple volatile organic compounds exposure on liver injury and risk of non-alcoholic fatty liver disease in a representative general adult population - Wei Liu; Shuting Cao; Da Shi; Linling Yu; Weihong Qiu; Weihong Chen; Bin Wang (Chemosphere, 2023)

Lateral impact behaviour of post-fire steel-reinforced concrete-filled steel tubular members: Experiment and evaluation method - Sun-Hang Ji; Wen-Da Wang; Wensu Chen; Yan-Li Shi; Wei Xian (Engineering Structures, 2023)

Development of all-cellulose sustainable composites from directionally aligned bamboo fiber scaffold with high strength, toughness, and low thermal conductivity - Cheng Qian; Yu-Tian Wang; Chun Shi; Hao-Ying Wang; Hai-Yan Yang; Jing Yang; Da-Wei Wang; Zheng-Jun Shi (Chemical Engineering Journal, 2023)

Cold-water coral diversity along the continental shelf margin of northwestern South China Sea - Mei-Xia Zhao; Yu Zhong; Shu-Qi Zhang; Pu Guo; Da-Peng Jiang; Hong-Qiang Yan; Jian-Wen Qiu; Qi Shi; Duan-Xin Chen (Marine Environmental Research, 2023)

A novel approach to examining the optimal use of the cooling effect of water bodies in urban planning - Zehongyu Kang; Hua Liu; Yuxin Lu; Xinyu Yang; Xin Zhou; Jingjing An; Da Yan; Xing Jin; Xing Shi (Building and Environment, 2023)

Impact of host plants on biological characteristics and Vg/VgR expression of Spodoptera frugiperda - Shi-Peng Han; Ya-Yuan Zhou; Da Wang; Qiu-Ju Qin; Peng Song; Yun-Zhuan He (Journal of Pest Science, 2023)

Correction to: Genome‑wide characterization of long terminal repeat retrotransposons provides insights into trait evolution of four cucurbit species - Hai‑Nan Liu; Mao‑Song Pei; Charles Ampomah‑Dwamena; Guang‑Qi He; Tong‑Lu Wei; Qiao‑Fang Shi; Yi‑He Yu; Da‑Long Guo (Functional & Integrative Genomics, 2023)

Genome-wide characterization of long terminal repeat retrotransposons provides insights into trait evolution of four cucurbit species - Hai-Nan Liu; Mao-Song Pei; Charles Ampomah-Dwamena; Guang-Qi He; Tong-Lu Wei; Qiao-Fang Shi; Yi-He Yu; Da-Long Guo (Functional & Integrative Genomics, 2023)

Comprehensive cell surface protein profiling of human mesenchymal stromal cells from peritoneal dialysis effluent and comparison with those from human bone marrow and adipose tissue - Ganggang Shi; Chong Yang; Lan Zhou; Ming Zong; Qiunong Guan; Gerald da Roza; Hao Wang; Hualin Qi; Caigan Du (Human Cell, 2023)
Peritoneal mesenchymal stromal cells (pMSCs) are isolated from peritoneal dialysis (PD) effluent, and treatment with the pMSCs reduces peritoneal membrane injury in rat model of PD. This study was designed to verify the identity of the pMSCs. pMSCs were grown in plastic dishes for 4–7 passages, and their cell surface phenotype was examined by staining with a panel of 242 antibodies. The positive stain of each target protein was determined by an increase in fluorescence intensity as compared with isotype controls in flow cytometrical analysis. Here, we showed that pMSCs predominantly expressed CD9, CD26, CD29, CD42a, CD44, CD46, CD47, CD49b, CD49c, CD49e, CD54, CD55, CD57, CD59, CD63, CD71, CD73, CD81, CD90, CD98, CD147, CD151, CD200, CD201, β2-micoglobulin, epithelial growth factor receptor, human leukocyte antigen (HLA) class 1, and, to a lesser extent, CD31, CD45RO, CD49a, CD49f, CD50, CD58, CD61, CD105, CD164, and CD166. These cells lacked expression of most hematopoietic markers such as CD11b, CD14, CD19, CD34, CD40, CD80, CD79, CD86, and HLA-DR. There was 38.55% difference in the expression of 83 surface proteins between bone marrow (BM)-derived MSCs and pMSCs, and 14.1% in the expression of 242 proteins between adipose tissue (AT)-derived MSCs and pMSCs. The BM-MSCs but not both AT-MSCs and pMSCs express cytokine receptors (IFNγR, TNFI/IIR, IL-1R, IL-4R, IL-6R, and IL-7R). In conclusion, pMSCs exhibited a typical cell surface phenotype of MSCs, which was not the same as on BM-MSCs or AT-MSCs, suggesting that the pMSCs may represent a different MSC lineage from peritoneal cavity.

Pre-oxidation coupled with charged covalent organic framework membranes for highly efficient removal of organic chloramines precursors in algae-containing water treatment - Da Sheng; Lingjun Bu; Shumin Zhu; Ruoxi Wu; Zhou Shi; Shiqing Zhou (Chemosphere, 2023)

Study on the protective performance of polymer layer to RC slabs under underwater explosions - Shucan Liu; Xiaohua Zhao; Hongyuan Fang; Da Liu; Mingsheng Shi (Ocean Engineering, 2023)

Hydroxypropyl-beta-Cyclodextrin embedded resveratrol regulates gut microbiota to prevent NAFLD via activating AMPK signaling pathway - Wenya Ke; Juan Huang; Yi Zhong; Yuhong Shi; Fen Yan; Da Huang; Yuanzi Wu; Houbing Zheng; Zuquan Weng (Food Bioscience, 2023)

Enterobacter sp. E1 increased arsenic uptake in Pteris vittata by promoting plant growth and dissolving Fe-bound arsenic - Aiting Li; Yingying Lu; Da Zhen; Ziheng Guo; Gejiao Wang; Kaixiang Shi; Shuijiao Liao (Chemosphere, 2023)

Spatiotemporal variations of the global compound heat wave and the drivers of its spatial heterogeneity - Lijun Jiang; Jiahua Zhang; Quan Liu; Xianglei Meng; Lamei Shi; Da Zhang; Mingming Xing (Journal of Cleaner Production, 2023)

Obesity modifies the association of environmental pyrethroid exposure with glucose homeostasis in the US general adults - Ruyi Liang; Xiaobing Feng; Da Shi; Bin Wang; Yongfang Zhang; Wei Liu; Linling Yu; Zi Ye; Min Zhou; Weihong Chen (Environmental Pollution, 2023)

Octyl gallate targeting the 3C-like protease exhibits highly efficient antiviral activity against swine enteric coronavirus PEDV - Mingjun Su; Baishuang Yin; Xiaoxu Xing; Zijian Li; Jiyu Zhang; Shufeng Feng; Lu Li; Feiyu Zhao; Xu Yang; Shiping Yu; Jun Wang; Yongchen Zhang; et al. (Veterinary Microbiology, 2023)

Physiological response and photosynthetic recovery to an extreme drought: Evidence from plants in a dry-hot valley savanna of Southwest China - Da Yang; Yang-Si-Ding Wang; Qin Wang; Yan Ke; Yun-Bing Zhang; Shi-Bao Zhang; Yong-Jiang Zhang; Nate G. McDowell; Jiao-Lin Zhang (Science of The Total Environment, 2023)

Associations of urinary 1,3-butadiene metabolite with glucose homeostasis, prediabetes, and diabetes in the US general population: Role of alkaline phosphatase - Ruyi Liang; Xiaobing Feng; Da Shi; Linling Yu; Meng Yang; Min Zhou; Yongfang Zhang; Bin Wang; Weihong Chen (Environmental Research, 2023)

Impacts of global urban expansion on natural habitats undermine the 2050 vision for biodiversity - Qiang Ren; Chunyang He; Qingxu Huang; Da Zhang; Peijun Shi; Wenlu Lu (Resources, Conservation and Recycling, 2023)

Insight into the mechanism of gasification fine slag enhanced flotation with selective dispersion flocculation - Da Shi; Jianbo Zhang; Huiquan Li; Shaopeng Li; Fayu He; Jiangshan Qu; Ruiqi Chang; Ganyu Zhu; Chennian Yang; Chenye Wang (Fuel, 2023)

Performance and application of a novel drainage anti-slide pile on accumulation landslide with a chair-like deposit-bedrock interface in the Three Gorges Reservoir area, China - Shi-lin Luo; Da Huang; Jian-bing Peng; Ailifeila Aierken; Zhao Li; Xi-bin Kuang; Roberto Tomás (Computers and Geotechnics, 2023)

Local Path Planning with Multiple Constraints for USV Based on Improved Bacterial Foraging Optimization Algorithm - Yang Long; Song Liu; Da Qiu; Changzhen Li; Xuan Guo; Binghua Shi; Mahmoud S. AbouOmar (Journal of Marine Science and Engineering, 2023)
The quality of unmanned surface vehicle (USV) local path planning directly affects its safety and autonomy performance. The USV local path planning might easily be trapped into local optima. The swarm intelligence optimization algorithm is a novel and effective method to solve the path-planning problem. Aiming to address this problem, a hybrid bacterial foraging optimization algorithm with a simulated annealing mechanism is proposed. The proposed algorithm preserves a three-layer nested structure, and a simulated annealing mechanism is incorporated into the outermost nested dispersal operator. The proposed algorithm can effectively escape the local optima. Convention on the International Regulations for Preventing Collisions at Sea (COLREGs) rules and dynamic obstacles are considered as the constraints for the proposed algorithm to design different obstacle avoidance strategies for USVs. The coastal port is selected as the working environment of the USV in the visual test platform. The experimental results show the USV can successfully avoid the various obstacles in the coastal port, and efficiently plan collision-free paths.

A novel protein domain is important for photosystem II complex assembly and photoautotrophic growth in angiosperms - Wei Li; Jiangfan Guo; Xue Han; Xiaowen Da; Kai Wang; Hongfei Zhao; Shi-Tang Huang; Bosheng Li; Hang He; Ruirui Jiang; Shichen Zhou; Peng Yan; et al. (Molecular Plant, 2023)

Transfer organic chloramines to monochloramine using two-step chlorination: A method to inhibit N-DBPs formation in algae-containing water treatment - Da Sheng; Lingjun Bu; Shumin Zhu; Lin Deng; Zhou Shi; Shiqing Zhou (Journal of Hazardous Materials, 2023)

Melatonin improves the removal and the reduction of Cr(VI) and alleviates the chromium toxicity by antioxidative machinery in Rhodobacter sphaeroides - Hao-Tian Mao; Lun-Xing Chen; Meng-Ying Zhang; Qiu-Yun Shi; Hong Xu; Da-Yan Zhang; Zhong-Wei Zhang; Ming Yuan; Shu Yuan; Huai-Yu Zhang; Yan-Qiu Su; Yang-Er Chen (Environmental Pollution, 2023)

Janus nanozyme based satellite structure immunosandwich colorimetric strategy for glycoproteins visual detection - Yi-Da Zhang; Chen Ma; Yan-Ping Shi (Chemical Engineering Journal, 2023)

DNAzymes-conjugated upconversion nanoamplicon for in-situ ultrasensitive detection and imaging of microRNA in vivo - Yi Zhang; Da Luo; Yin Zhang; Qi-Hai Zhang; Qing-Yuan Ji; Shi-Kang Zhou; Shan Huang; Li-li Li; Feng Lu; Wei-Feng Yao; Fang-Fang Cheng; Jun-Jie Zhu; et al. (Chemical Engineering Journal, 2023)

Evaluation of deep learning algorithms for landslide susceptibility mapping in an alpine-gorge area: a case study in Jiuzhaigou County - Di Wang; Rong-hao Yang; Xiao Wang; Shao-da Li; Jun-xiang Tan; Shi-qi Zhang; Shuo-you Wei; Zhang-ye Wu; Chao Chen; Xiao-xia Yang (Journal of Mountain Science, 2023)

A reliable and effective sample preparation protocol of MALDI-TOF-MSI for lipids imaging analysis in hard and dry cereals - Yan-Xia Zhang; Yi-Da Zhang; Yan-Ping Shi (Food Chemistry, 2023)

Generation of reactive oxygen species through dissolved oxygen activation on defected porous carbon for efficient degradation of antibiotics - Jiaming Liu; Zhangwei Yao; Genping Qiu; Yinhua Wan; Weijie Song; Huifeng Zeng; Feifei Yang; Da Zhao; Wenjing Yuan; Peihai Ju; Ruixi Lin; Hengcheng Zhou; et al. (Chemical Engineering Journal, 2023)

Exposures to volatile organic compounds, serum vitamin D, and kidney function: association and interaction assessment in the US adult population - Wei Liu; Shuting Cao; Jixuan Ma; Da Shi; Linling Yu; Zi Ye; Meng Yang; Bin Wang; Weihong Chen (Environmental Science and Pollution Research, 2023)

Actinomycin D: a novel Pseudomonas aeruginosa quorum sensing inhibitor from the endophyte Streptomyces cyaneochromogenes RC1 - Yue-Xiang Zeng; Jun-Sheng Liu; Ying-Jie Wang; Shi Tang; Da-Yong Wang; Shi-Ming Deng; Ai-Qun Jia (World Journal of Microbiology and Biotechnology, 2022)

Correction to: Protective effects of fowl‑origin cadmium‑tolerant lactobacillus against sub‑chronic cadmium‑induced toxicity in chickens - Da‑Wei Chen; Hui‑Jia Li; YinYin Liu; Li‑Na Ma; Jun‑Hua Pu; JunXian Lu; Xiu‑Jun Tang; Yu‑shi Gao (Environmental Science and Pollution Research, 2022)

Protective effects of fowl-origin cadmium-tolerant lactobacillus against sub-chronic cadmium-induced toxicity in chickens - Da-Wei Chen; Hui-Jia Li; YinYin Liu; Li-Na Ma; Jun-Hua Pu; JunXian Lu; Xiu-Jun Tang; Yu-shi Gao (Environmental Science and Pollution Research, 2022)

Homocysteine-Induced Disturbances in DNA Methylation Contribute to Development of Stress-Associated Cognitive Decline in Rats - Shi-Da Wang; Xue Wang; Yun Zhao; Bing-Hua Xue; Xiao-Tian Wang; Yu-Xin Chen; Zi-Qian Zhang; Ying-Rui Tian; Fang Xie; Ling-Jia Qian (Neuroscience Bulletin, 2022)

Association of caffeine and caffeine metabolites with obesity among children and adolescents: National Health and Nutrition Examination Survey (NHANES) 2009–2014 - Linling Yu; Hong Mei; Da Shi; Xing Wang; Man Cheng; Lieyang Fan; Yang Xiao; Ruyi Liang; Bin Wang; Meng Yang; Weihong Chen (Environmental Science and Pollution Research, 2022)

Characteristics of N2O release from polluted creeks in the Taihu Lake Basin: sources and microbial populations - Da Li; Linglong Shi; Shuangzhen Guo; Lihua Zang (Aquatic Sciences, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Urinary polycyclic aromatic hydrocarbon metabolites and depression: a cross-sectional study of the National Health and Nutrition Examination Survey 2005–2016 - Xiaobing Feng; Ruyi Liang; Da Shi; Dongming Wang; Yanjun Guo; Weihong Qiu; Man Cheng; Tao Xu; Chaoqian Dong; Min Zhou; Weihong Chen (Environmental Science and Pollution Research, 2022)

Phenolic glycosides from Sanguisorba officinalis and their anti-inflammatory effects - Jin-feng Chen; Lu Tan; Feng Ju; Qi-xuan Kuang; Tian-long Yang; Fang Deng; Yu-cheng Gu; Li-shi Jiang; Yun Deng; Da-le Guo (Natural Product Research, 2022)

Dissecting the Neural Circuitry for Pain Modulation and Chronic Pain: Insights from Optogenetics - Fang Guo; Yu Du; Feng-Hui Qu; Shi-Da Lin; Zhong Chen; Shi-Hong Zhang (Neuroscience Bulletin, 2022)
Pain is an unpleasant sensory and emotional experience associated with, or resembling that associated with, actual or potential tissue damage. The processing of pain involves complicated modulation at the levels of the periphery, spinal cord, and brain. The pathogenesis of chronic pain is still not fully understood, which makes the clinical treatment challenging. Optogenetics, which combines optical and genetic technologies, can precisely intervene in the activity of specific groups of neurons and elements of the related circuits. Taking advantage of optogenetics, researchers have achieved a body of new findings that shed light on the cellular and circuit mechanisms of pain transmission, pain modulation, and chronic pain both in the periphery and the central nervous system. In this review, we summarize recent findings in pain research using optogenetic approaches and discuss their significance in understanding the pathogenesis of chronic pain.

Biocompatible self-healing hydrogels based on boronic acid-functionalized polymer and laponite nanocomposite for water pollutant removal - Xue-Ting Wang; Xudong Deng; Tuo-Di Zhang; Xi Zhang; Wen-Pu Shi; Jialiang Lai; Hongwei Zhou; Ya-Jing Ye; Chen-Yan Zhang; Da-Chuan Yin (Environmental Chemistry Letters, 2022)

Three new cycloart-7-ene triterpenoid glycosides from Cimicifuga dahurica and their anti-inflammatory effects - Qian-Qian Pang; Yu-Dan Mei; Yuan-Chu Zhang; Ling-Xian Liu; Dan-Feng Shi; Da-Bo Pan; Xin-Sheng Yao; Hai-Bo Li; Yang Yu (Natural Product Research, 2021)

Super-resolution performance studies for orbital-angular-momentum-based imaging radar - Ting Yang; Hongyin Shi; Jianwen Guo; Da Liu; Zhijun Qiao (International Journal of Remote Sensing, 2021)

A new nitrogen-containing iridoid glycoside from lonicera macranthoides - Yu-Dan Mei; Hai-Bo Li; Ling-Xian Liu; Dan-feng Shi; Da-bo Pan; Xin-Sheng Yao; Yang Yu (Natural Product Research, 2021)

Can feeding sound attract flower fish (Ptychobarbus kaznakovi)? - Mingyun Wang; Qingfu Wang; Ma Ni; Wa Da; Yajun Wang; Xiaotao Shi; Guoyong Liu (Journal of Comparative Physiology A, 2021)

Regional climates shape the biogeographic history of a broadly distributed freshwater crab species complex - Boyang Shi; Da Pan; Yufang Sun; Xiaorui Liu; Xiulin Lv; Neil Cumberlidge; Hongying Sun (Journal of Biogeography, 2021)
Aim The evolutionary importance of paleoclimate regimes has been noted in biogeographic studies. However, little is known about how paleoclimate differences shaped the biogeographic pattern and diversification history of the freshwater fauna in important zoogeographical boundary regions. Here, we aim to investigate how past regional climatic differences have shaped the biogeographic history of the inland aquatic fauna in China using an endemic freshwater crab species complex found on both sides of the Qinling Mountains–Huaihe River Line (QHL), a critical ecological boundary in eastern China, as a model system. Location Eastern China, the Qinling Mountains–Huaihe River Line. Taxon The Sinopotamon yangtsekiense species complex. Methods A total of 482 individuals of Sinopotamon yangtsekiense sensu lato were collected from 34 localities throughout its entire distributional range. The phylogeographic analyses of population structure, morphological and genetic variations, and demographic dynamics were made based on multiple mtDNA and nuDNA loci and on morphological traits. Fine‐tuned ecological niche modeling was used to reconstruct the location of climatically suitable areas that existed during the Last Glacial Maximum. Results The divergence of two freshwater crab lineages across the QHL correlated with significant past variations in monsoon intensity and with the location of multiple refuges. The divergence time was broadly consistent with the timing of the critical paleoclimate transition event in the mid‐Pleistocene (95% HPD, 0.48–1.06 Ma). Each freshwater crab lineage has evolved distinct male genital traits associated with their isolation in areas with different precipitation rates and temperatures in the past. The patterns of crab distribution observed today reflect past contractions of the two lineages in response to glacial and interglacial cycles during the Pleistocene, followed by their subsequent rapid expansion after the Last Glacial Maximum (~15 kya). Main conclusions Populations of the widespread species Sinopotamon yangtsekiense s.l. experienced a deep division in the past that led to the phylogeographical isolation observed today. The two main drivers of genetic isolation in this taxon were (a) differences in the intensity of the monsoons on each side of the QHL boundary during the mid‐Pleistocene, and (b) isolation of different populations of S. yangtsekiense s.l. in a number of separate refuges during the LGM.

Deformation characteristics and reactivation mechanisms of the Outang ancient landslide in the Three Gorges Reservoir, China - Shi-Lin Luo; Da Huang (Bulletin of Engineering Geology and the Environment, 2020)

Molecular characterization of an emerging reassortant mammalian orthoreovirus in China - Dandan Ye; Zhaoyang Ji; Hongyan Shi; Jianfei Chen; Da Shi; Liyan Cao; Jianbo Liu; Mingwei Li; Hui Dong; Zhaoyang Jing; Xiaobo Wang; Qiuge Liu; et al. (Archives of Virology, 2020)

Chemical characterization of constituents from Polygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation - Ting Zeng; Yan-Ran Tang; Bin Li; Shumaila Tasneem; Han-Wen Yuan; Yan-Zhe Jia; Muhammad Daniyal; Nusrat Hussain; Wen-Miao Wang; Da-Lei Zuo; Li-Min Gong; Bin Liu; et al. (Natural Product Research, 2020)

Scientific and technological power and international cooperation in the field of natural hazards: a bibliometric analysis - Jing-Li Fan; Shuo Shen; Jian-Da Wang; Shi-Jie Wei; Xian Zhang; Ping Zhong; Hang Wang (Natural Hazards, 2020)

Fungi isolated from host protocorms accelerate symbiotic seed germination in an endangered orchid species (Dendrobium chrysotoxum) from southern China - Shi-Cheng Shao; Qiu-Xia Wang; Kingly C. Beng; Da-Ke Zhao; Hans Jacquemyn (Mycorrhiza, 2020)

Serotonin-induced miR-221/222 contribute to the activation of hepatic stellate cells - Yi Xiang; Yu-Shui Ma; Ji-Bin Liu; Zhi-Jun Wu; Xiao-Ping Wang; Li-Ping Liu; Gao-Ren Wang; Da Fu; Wei Shi (Biologia, 2020)

Contamination characteristics of heavy metals in particle size fractions from street dust from an industrial city, Central China - Ping Zhong; Jia-Quan Zhang; Da-Mao Xu; Qian Tian; Tian-Peng Hu; Xiang-Yi Gong; Chang-Lin Zhan; Shan Liu; Xin-Li Xing; Shi-Hua Qi (Air Quality, Atmosphere & Health, 2020)

Development of a rapid and sensitive europium (III) chelate microparticle-based lateral flow test strip for the detection and epidemiological surveillance of porcine epidemic diarrhea virus - Jianbo Liu; Hongyan Shi; Guangyi Cong; Jianfei Chen; Xin Zhang; Da Shi; Liyan Cao; Xiaobo Wang; Jialin Zhang; Zhaoyang Ji; Zhaoyang Jing; Li Feng (Archives of Virology, 2020)

Microarc oxidation surface of titanium implants promote osteogenic differentiation by activating ERK1/2-miR-1827-Osterix - Liu Liu; Da Zeng; Yanwen Chen; Junbo Zhou; Yunyang Liao; Bin Shi (In Vitro Cellular & Developmental Biology - Animal, 2020)

Development of an indirect ELISA for detecting porcine deltacoronavirus IgA antibodies - Manman Lu; Qiuge Liu; Xiaobo Wang; Jialin Zhang; Xin Zhang; Da Shi; Jianbo Liu; Hongyan Shi; Jianfei Chen; Li Feng (Archives of Virology, 2020)

Rare variants in FANCA induce premature ovarian insufficiency - Xi Yang; Xiaojin Zhang; Jiao Jiao; Feng Zhang; Yuncheng Pan; Qiqi Wang; Qing Chen; Baozhu Cai; Shuyan Tang; Zixue Zhou; Siyuan Chen; Hao Yin; et al. (Human Genetics, 2019)
Premature ovarian insufficiency (POI) is a major cause of reduced female fertility and affects approximately 1% women under 40 years of age. Recent advances emphasize the genetic heterogeneity of POI. Fanconi anemia (FA) genes, traditionally known for their essential roles in DNA repair and cytogenetic instability, have been demonstrated to be involved in meiosis and germ cell development. Here, we conducted whole-exome sequencing (WES) in 50 Han Chinese female patients with POI. Rare missense variants were identified in FANCA ( Fanconi anemia complementation group A ): c.1772G > A (p.R591Q) and c.3887A > G (p.E1296G). Both variants are heterozygous in the patients and very rare in the human population. In vitro functional studies further demonstrated that these two missense variants of FANCA exhibited reduced protein expression levels compared with the wild type, suggesting the partial loss of function. Moreover, mono-ubiquitination levels of FANCD2 upon mitomycin C stimulation were significantly reduced in cells overexpressing FANCA variants. Furthermore, a loss-of-function mutation of Fanca was generated in C57BL/6 mice for in vivo functional assay. Consistently, heterozygous mutated female mice ( Fanca + / − ) showed reduced fertility and declined numbers of follicles with aging when compared with the wild-type female mice. Collectively, our results suggest that heterozygous pathogenic variants in FANCA are implicated in non-syndromic POI in Han Chinese women, provide new insights into the molecular mechanisms of POI and highlight the contribution of FANCA variants in female subfertility.

Glacier change in the Tanggula Mountains, Tibetan Plateau, in 1969–2015 - Hong-yu Duan; Xiao-jun Yao; Shi-yin Liu; Yong-peng Gao; Miao-miao Qi; Juan Liu; Da-hong Zhang; Xiao-feng Li (Journal of Mountain Science, 2019)

Isolation and characterization of a novel strain (YH01) of Micropterus salmoides rhabdovirus and expression of its glycoprotein by the baculovirus expression system - Sun-jian Lyu; Xue-mei Yuan; Hai-qi Zhang; Wei-da Shi; Xiao-ying Hang; Li Liu; Ying-lei Wu (Journal of Zhejiang University-SCIENCE B, 2019)

Correction to: Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2019)

Mapping and cloning of quantitative trait loci for phosphorus efficiency in crops: opportunities and challenges - Wei Wang; Guang-Da Ding; Philip John White; Xiao-Hua Wang; Ke-Mo Jin; Fang-Sen Xu; Lei Shi (Plant and Soil, 2019)

Population Scale Retrospective Analysis Reveals Potential Risk of Cholestasis in Pregnant Women Taking Omeprazole, Lansoprazole, and Amoxicillin - Yonghong Zhang; Da Shi; Ruben Abagyan; Weina Dai; Mingyang Dong (Interdisciplinary Sciences: Computational Life Sciences, 2019)

Analysis of Rock Mass Stability Based on Mining-Induced Seismicity: A Case Study at the Hongtoushan Copper Mine in China - Jian-po Liu; Shi-da Xu; Yuan-hui Li; Gang Lei (Rock Mechanics and Rock Engineering, 2019)

Whole sequence analysis indicates a recent southern origin of Mongolian Y-chromosome C2c1a1a1-M407 - Yun-Zhi Huang; Lan-Hai Wei; Shi Yan; Shao-Qing Wen; Chuan-Chao Wang; Ya-Jun Yang; Ling-Xiang Wang; Yan Lu; Chao Zhang; Shu-Hua Xu; Da-Li Yao; Li Jin; et al. (Molecular Genetics and Genomics, 2018)

Uhrf2 deletion impairs the formation of hippocampus-dependent memory by changing the structure of the dentate gyrus - Xiao-Rong Chen; Shi-Cheng Sun; Shuai-Wen Teng; Liang Li; Yi-Fan Bie; Hui Yu; Da-Li Li; Zhe-Yu Chen; Yue Wang (Brain Structure and Function, 2018)

Metatranscriptome analysis reveals environmental and diel regulation of a Heterosigma akashiwo (raphidophyceae) bloom - Nanjing Ji; Lingxiao Lin; Ling Li; Liying Yu; Yaqun Zhang; Hao Luo; Meizhen Li; Xinguo Shi; Da‐Zhi Wang; Senjie Lin (Environmental Microbiology, 2018)
Summary Despite numerous laboratory studies on physiologies of harmful algal bloom (HAB) species, physiologies of these algae during a natural bloom are understudied. Here, we investigated a bloom of the raphidophyte Heterosigma akashiwo in the East China Sea in 2014 using metabarcode (18S rDNA) and metatranscriptome sequencing. Based on 18S rDNA analyses, the phytoplankton community shifted from high diversity in the pre‐bloom stage to H. akashiwo predominance during the bloom. A sharp decrease in ambient dissolved inorganic phosphate and strong up‐regulation of phosphate and dissolved organic phosphorus (DOP) uptake genes, including the rarely documented (ppGpp)ase, in H. akashiwo from pre‐bloom to bloom was indicative of rapid phosphorus uptake and efficient utilization of DOP that might be a driver of the H. akashiwo bloom. Furthermore, observed up‐regulated expression of mixotrophy‐related genes suggests potential contribution of mixotrophy to the bloom. Accelerating photosynthetic carbon fixation was also implied by the up‐regulation of carbonic anhydrase genes during the bloom. Notably, we also observed a strong morning‐to‐afternoon shift in the expression of many genes. Our findings provide insights into metabolic processes likely important for H. akashiwo bloom formation, and suggest the need to consider timing of sampling in field studies on this alga.

Detection and complete genome characteristics of Posavirus 1 from pigs in China - Jianfei Chen; Manman Lu; Tianxin Ma; Liyan Cao; Xiangdong Zhu; Xin Zhang; Da Shi; Hongyan Shi; Jianbo Liu; Li Feng (Virus Genes, 2018)

Investigation of the anisotropy of black shale in dynamic tensile strength - Xiaoshan Shi; Da’an Liu; Wei Yao; Yirui Shi; Tiewu Tang; Bonan Wang; Weige Han (Arabian Journal of Geosciences, 2018)

Stream temperature dynamics in Nam Co basin, southern Tibetan Plateau - Tan-guang Gao; Shi-chang Kang; Ting-jun Zhang; Da-qing Yang; Jian-guo Shang; Xiang Qin (Journal of Mountain Science, 2017)

Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2017)
Cystatin SN (CST1) belongs to the type 2 cystatin (CST) superfamily, which restricts the proteolytic activities of cysteine proteases. CST1 has been recently considered to be involved in the development of several human cancers. However, the prognostic significance and function of CST1 in breast cancer remains unknown. In the current study, we found that CST1 was generally upregulated in breast cancer at both mRNA and protein level. Furthermore, overall survival (OS) and disease-free survival (DFS) in the low CST1 expression subgroup were significantly superior to the high CST1 expression subgroup (OS, p < 0.001; DFS, p < 0.001), which indicated that CST1 expression level was closely correlated to the survival risk of these patients. Univariate and multivariate analyses demonstrated that CST1 expression was an independent prognostic factor, the same as ER status and nodal status. Next, CST1 overexpression promoted breast cancer cell proliferation, clonogenicity, migration, and invasion abilities. By contrast, knockdown of CST1 attenuated these malignant characteristics in breast cancer cells. Collectively, our study indicates that CST1 cannot only serve as a significant prognostic indicator but also as a potential therapeutic target for breast cancer. Key messages High CST1 expression is negatively correlated with survival of breast cancer patients. CST1 promotes cell proliferation, clone formation, and metastasis in breast cancer cells. CST1 is a novel potential prognostic biomarker and therapeutic target for breast cancer.

Boron-bridged RG-II and calcium are required to maintain the pectin network of the Arabidopsis seed mucilage ultrastructure - Da-chuan Shi; Juan Wang; Rui-bo Hu; Gong-ke Zhou; Malcolm A. O’Neill; Ying-zhen Kong (Plant Molecular Biology, 2017)

An efficient one-pot synthesis of functionalized chromeno[4,3-b]pyridine derivatives under catalyst-free conditions - Yong-Xiang Zheng; Zhan Xun; Juan-Juan Zhang; Zhi-Bin Huang; Da-Qing Shi (Molecular Diversity, 2017)

Alismol, a Sesquiterpenoid Isolated from Vladimiria souliei, Suppresses Proinflammatory Mediators in Lipopolysaccharide-Stimulated Microglia - Dongdong Shi; Xiaoqiang Song; Yuanqiang Guo; Jing Xu; Yu Liu; Jingling Zhang; Chun-Ai Cui; Da-Qing Jin (Journal of Molecular Neuroscience, 2017)

Identification of the Genetic Cause for Childhood Disintegrative Disorder by Whole-Exome Sequencing - Zhu Wen; Tian-Lin Cheng; Da-Zhi Yin; Shi-Bang Sun; Zheng Wang; Shun-Ying Yu; Yi Zhang; Zilong Qiu; Ya-Song Du (Neuroscience Bulletin, 2017)

Elliptic Shape Prior Dynamic Programming for Accurate Vessel Segmentation in MRI Sequences with Automated Optimal Parameter Selection - Da-Chuan Cheng; Sin-Kuo Chai; Shi-Rong Xu; Shing-Hong Liu (Journal of Medical and Biological Engineering, 2016)

Highly selective and efficient biotransformation of linarin to produce tilianin by naringinase - Pan Cui; Tong-Yi Dou; Shi-Yang Li; Jun-Xia Lu; Li-Wei Zou; Ping Wang; Yan-Ping Sun; Da-Cheng Hao; Guang-Bo Ge (Biotechnology Letters, 2016)

Human amniotic epithelial stem cells promote wound healing by facilitating migration and proliferation of keratinocytes via ERK, JNK and AKT signaling pathways - Bin Zhao; Jia-Qi Liu; Zhao Zheng; Jun Zhang; Shu-Yue Wang; Shi-Chao Han; Qin Zhou; Hao Guan; Chao Li; Lin-Lin Su; Da-Hai Hu (Cell and Tissue Research, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Multiple roles of oxygen in the photoinactivation and dynamic repair of Photosystem II in spinach leaves - Da-Yong Fan; Zi-Piao Ye; Shi-Chang Wang; Wah Soon Chow (Photosynthesis Research, 2016)

Erratum to: Immunogenicity and antigenic relationships among spike proteins of porcine epidemic diarrhea virus subtypes G1 and G2 - Xiaobo Wang; Jianfei Chen; Da Shi; Hongyan Shi; Xin Zhang; Jing Yuan; Shibo Jiang; Li Feng (Archives of Virology, 2016)

Immunogenicity and antigenic relationships among spike proteins of porcine epidemic diarrhea virus subtypes G1 and G2 - Xiaobo Wang; Jianfei Chen; Da Shi; Hongyan Shi; Xin Zhang; Jing Yuan; Shibo Jiang; Li Feng (Archives of Virology, 2016)

Formation of radial symmetric needle-like rosette leaves in Arabidopsis - Jiang-Ping Song; Da-Hui Liu; Yi-Bo Wang; Ya-Na Shi (Biologia, 2015)

Identification of insecticidal constituents of the essential oils of Dahlia pinnata Cav. against Sitophilus zeamais and Sitophilus oryzae - Da-Cheng Wang; Da-Ren Qiu; Li-Na Shi; Hong-Yu Pan; Ya-Wei Li; Jin-Zhu Sun; Ying-Jie Xue; Dong-Sheng Wei; Xiang Li; Ya-Mei Zhang; Jian-Chun Qin (Natural Product Research, 2015)

Foxl2 of the Hong Kong catfish (Clarias fuscus): cDNA cloning, tissue distribution and changes in gene expression towards methyltestosterone, estradiol and letrozole exposure of the fries during gonadal differentiation - Si-ping Deng; Chun-hua Zhu; Jing Sun; Wen-da Wang; Tian-li Wu; Hua-pu Chen; Shang-li Shi; Guang-li Li (Genes & Genomics, 2015)

Synthesis and evaluation of the anti-inflammatory activity of quinoline derivatives - Xiang Wen; Shi-Ben Wang; Da-Chuan Liu; Guo-Hua Gong; Zhe-Shan Quan (Medicinal Chemistry Research, 2015)

17β-Estradiol protects against apoptosis induced by interleukin-1β in rat nucleus pulposus cells by down-regulating MMP-3 and MMP-13 - Si-Dong Yang; Da-Long Yang; Ya-Peng Sun; Bao-Lin Wang; Lei Ma; Shi-Qing Feng; Wen-Yuan Ding (Apoptosis, 2015)

An efficient three-component synthesis of highly functionalized tetrahydroacenaphtho[1,2- $$b$$ b ]indolone derivatives catalyzed by L-proline - Juan-Juan Zhang; Xian Feng; Xue-Cheng Liu; Zhi-Bin Huang; Da-Qing Shi (Molecular Diversity, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Synthesis and evaluation of anticonvulsant and antidepressant activities of 7-alkyl-7H-tetrazolo[1,5-g]purine derivatives - Shi-Ben Wang; Xian-Qing Deng; Da-Chuan Liu; Hong-Jian Zhang; Zhe-Shan Quan (Medicinal Chemistry Research, 2014)

Architecture and development of a multi-stage Baiyun submarine slide complex in the Pearl River Canyon, northern South China Sea - Lei Wang; Shi-Guo Wu; Qing-Ping Li; Da-Wei Wang; Shao-Ying Fu (Geo-Marine Letters, 2014)

Icariin-Mediated Inhibition of NF-κB Activity Enhances the In Vitro and In Vivo Antitumour Effect of 5-Fluorouracil in Colorectal Cancer - De-Bing Shi; Xin-Xiang Li; Hong-Tu Zheng; Da-Wei Li; Guo-Xiang Cai; Jun-Jie Peng; Wei-Lie Gu; Zu-Qing Guan; Ye Xu; San-Jun Cai (Cell Biochemistry and Biophysics, 2014)

Synthesis and anticonvulsant activity evaluation of 7-alkoxy-2,4-dihydro-1H-benzo[b][1,2,4]triazolo[4,3-d][1,4]thiazin-1-ones in various murine experimental seizure models - Xu Cao; Shi-Ben Wang; Xian-Qing Deng; Da-Chuan Liu; Zhe-Shan Quan (Medicinal Chemistry Research, 2014)

Endogenous Subventricular Zone Neural Progenitors Contribute to the Formation and Hyperexcitability of Experimental Model of Focal Microgyria - Hai-Feng Shu; Yong-Qin Kuang; Shi-Yong Liu; Si-Xun Yu; Chun-Qing Zhang; Da-Hai Zheng; Jian-Wen Gu; Hui Yang (Journal of Molecular Neuroscience, 2014)

Expressions of ER, PR, HER-2, COX-2, and VEGF in Primary and Relapsed/Metastatic Breast Cancers - Li Sun; Da-hai Yu; San-Yuan Sun; Shi-Chao Zhuo; Su-sheng Cao; Ling Wei (Cell Biochemistry and Biophysics, 2014)

Porous-grain-upper-boundary model and its application to Tarim Basin carbonates - Yu-Qian Guo; Hong-Da Ma; Kai-Bo Shi; Hong Cao; Lu-Zhong Huang; Feng-Chang Yao; Tian-Yue Hu (Applied Geophysics, 2013)

Molecular characterization of a porcine kobuvirus variant strain in China - Da Shi; Sha Zhang; Jianfei Chen; Hongyan Shi; Xin Zhang; Li Feng (Archives of Virology, 2013)

High prevalence of torque teno sus virus in China and genetic diversity of the 5’ non-coding region - Shao-Lun Zhai; Jin-Xue Long; Wen-Kang Wei; Qin-Ling Chen; Man-Lin Luo; Dian-Hong Lv; Da-Cheng Wu; Fei Gao; Shi-Shan Yuan; Guang-Zhi Tong; Zu-Zhang Wei (Archives of Virology, 2013)

Down-regulation of eIF5A-2 prevents epithelial-mesenchymal transition in non-small-cell lung cancer cells - Guo-dong Xu; Xin-bao Shi; Le-bo Sun; Qing-yun Zhou; Da-wei Zheng; Huo-shun Shi; Yong-liang Che; Zi-shan Wang; Guo-feng Shao (Journal of Zhejiang University-SCIENCE B, 2013)

Genetic variation of nucleocapsid genes of porcine epidemic diarrhea virus field strains in China - Jianfei Chen; Xiaozhen Liu; Hongwu Lang; Zhongtian Wang; Da Shi; Hongyan Shi; Xin Zhang; Li Feng (Archives of Virology, 2013)

SHRIMP U-Pb zircon geochronology and Nd-Sr isotopic study of the Mamianshan Group: implications for the Neoproterozoic tectonic development of southeast China - Da Zhang; Ganguo Wu; Yongjun Di; Xinqi Yu; Yuruo Shi; Xiangxin Zhang; Qunfeng Wang; Huojian Huang (International Geology Review, 2013)

Molecular characterization and expression analysis of GlHMGS, a gene encoding hydroxymethylglutaryl-CoA synthase from Ganoderma lucidum (Ling-zhi) in ganoderic acid biosynthesis pathway - Ang Ren; Xiang Ouyang; Liang Shi; Ai-Liang Jiang; Da-Shuai Mu; Meng-Jiao Li; Qin Han; Ming-Wen Zhao (World Journal of Microbiology and Biotechnology, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Polymorphisms of the Interleukin 6 gene contribute to cervical cancer susceptibility in Eastern Chinese women - Ting-Yan Shi; Mei-Ling Zhu; Jing He; Meng-Yun Wang; Qiao-Xin Li; Xiao-Yan Zhou; Meng-Hong Sun; Zhi-Ming Shao; Ke-Da Yu; Xi Cheng; Xiaohua Wu; Qingyi Wei (Human Genetics, 2013)

Wnt/β-catenin signaling induces the aging of mesenchymal stem cells through promoting the ROS production - Da-yong Zhang; Yu Pan; Chong Zhang; Bing-xi Yan; Shan-shan Yu; Dong-ling Wu; Meng-meng Shi; Kai Shi; Xin-xiao Cai; Shuang-shuang Zhou; Jun-bo Wang; Jian-ping Pan; et al. (Molecular and Cellular Biochemistry, 2013)

Increased Expression of TRPV1 in the Cortex and Hippocampus from Patients with Mesial Temporal Lobe Epilepsy - Fei-Ji Sun; Wei Guo; Da-Hai Zheng; Chun-Qing Zhang; Song Li; Shi-Yong Liu; Qing Yin; Hui Yang; Hai-Feng Shu (Journal of Molecular Neuroscience, 2013)

Comparative study of four rice cultivars with different levels of cadmium tolerance - Xiao Wang; Zhong-Wei Zhang; Shi-Hua Tu; Wen-Qiang Feng; Fei Xu; Feng Zhu; Da-Wei Zhang; Jun-Bo Du; Shu Yuan; Hong-Hui Lin (Biologia, 2013)

The screening and preliminary construction of quality mutant population for cultivar “Nipponbare” in japonica rice (Oryza sativa) - Da Peng Zhang; Jian Guo Wu; Guan Li; Chun Hai Shi (Biologia, 2012)

Clinical significance of detection of antibodies to fetal and adult acetylcholine receptors in myasthenia gravis - Qi-Guang Shi; Zhi-Hong Wang; Xiao-Wei Ma; Da-Qi Zhang; Chun-Sheng Yang; Fu-Dong Shi; Li Yang (Neuroscience Bulletin, 2012)

Multi-environment mapping and meta-analysis of 100-seed weight in soybean - Ya-nan Sun; Jun-bo Pan; Xiang-lin Shi; Xiang-yu Du; Qiong Wu; Zhao-ming Qi; Hong-wei Jiang; Da-wei Xin; Chun-yan Liu; Guo-hua Hu; Qing-shan Chen (Molecular Biology Reports, 2012)

Lamiolactone, a new iridoid lactone from Lamiophlomis rotata - Jun-Jie Tan; Jun-Ming Tan; Chang-Heng Tan; Shi-Jin Qu; Da-Yuan Zhu (Natural Product Research, 2012)

Three new secolignan glycosides from Urtica fissa E. Pritz - Bao-min Feng; Hai-hong Qin; Hui-guo Wang; Li-ying Shi; Da-yong Yu; Bao-quan Ji; Qi Zhao; Yong-qi Wang (Journal of Natural Medicines, 2012)

Differential DNA Methylation Status Between Human Preadipocytes and Mature Adipocytes - Jin-gai Zhu; Li Xia; Chen-bo Ji; Chun-mei Zhang; Guan-zhong Zhu; Chun-mei Shi; Lin Chen; Da-ni Qin; Xi-rong Guo (Cell Biochemistry and Biophysics, 2012)

Adaptive evolution of context-dependent style curvature in some species of the Malvaceae: a molecular phylogenetic approach - Cheng-Jiang Ruan; Shi-Chao Chen; Qun Li; Jaime A. Teixeira da Silva (Plant Systematics and Evolution, 2011)

Effect of dietary fatty acids on serum parameters, fatty acid compositions, and liver histology in Shaoxing laying ducks - Wei-meng Liu; Shu-jing Lai; Li-zhi Lu; Fang-xiong Shi; Jing Zhang; Yu Liu; Bo Yu; Zheng-rong Tao; Jun-da Shen; Guo-qin Li; De-qian Wang; Jin-jun Li; et al. (Journal of Zhejiang University-SCIENCE B, 2011)

Analysis of the fungi community in multiple- and single-grains Zaopei from a Luzhou-flavor liquor distillery in western China - Si Shi; Lei Zhang; Zheng-yun Wu; Wen-xue Zhang; Yu Deng; Fang-da Zhong; Jia-min Li (World Journal of Microbiology and Biotechnology, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

Retrieval of chlorophyll a concentration from a fluorescence enveloped area using hyperspectral data - Fen-Fen Liu; Chu-Qun Chen; Shi-Lin Tang; Da-Zhao Liu (International Journal of Remote Sensing, 2011)

Rapid simultaneous screening of seven clinically important enteric pathogens using a magnetic bead based DNA microarray - Hong Sun; Qiu-Hua Mo; Ji-Can Lin; Ze Yang; Cheng-Ning Tu; Da-Yong Gu; Lei Shi; Wei-Ping Lu (World Journal of Microbiology and Biotechnology, 2011)

Laboratory study of fluid viscosity induced ultrasonic velocity dispersion in reservoir sandstones - Tao He; Chang-Chun Zou; Fa-Gen Pei; Ke-Ying Ren; Fan-Da Kong; Ge Shi (Applied Geophysics, 2010)

Morphologic observation and classification criteria of atretic follicles in guinea pigs - Wei Wang; Hong-lin Liu; Wei Tian; Fen-fen Zhang; Yan Gong; Jin-wei Chen; Da-gan Mao; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2010)

Physicochemical evolution and positive selection of the gymnosperm matK proteins - Da Cheng Hao; Jun Mu; Shi Lin Chen; Pei Gen Xiao (Journal of Genetics, 2010)

Molecular evolution and positive Darwinian selection of the chloroplast maturase matK - Da Cheng Hao; Shi Lin Chen; Pei Gen Xiao (Journal of Plant Research, 2010)

Mutational analysis of Arabidopsis PP2CA2 involved in abscisic acid signal transduction - Xin-Hong Guo; Ke-Qin Deng; Jie Wang; Da-Shi Yu; Qiong Zhao; Xuan-Ming Liu (Molecular Biology Reports, 2010)

Molecular phylogeny, long-term evolution, and functional divergence of flavin-containing monooxygenases - Da Cheng Hao; Shi Lin Chen; Jun Mu; Pei Gen Xiao (Genetica, 2009)

Two new N -oxide Lycopodium alkaloids from Huperzia serrata - Heng-Bin Wang; Chang-Heng Tan; Jun-Jie Tan; Shi-Jin Qu; Yi-Lei Chen; Yi-Ming Li; Shan-Hao Jiang; Da-Yuan Zhu (Natural Product Research, 2009)

Low Genetic Variability of Domestic Muscovy Duck (Cairina moschata) in China Revealed by Mitochondrial DNA Control Region Sequences - Shi-Yi Chen; Da-Qian He; Yi-Ping Liu (Biochemical Genetics, 2009)

Intercellular adhesion molecule-1 gene K469E polymorphism and ischemic stroke: a case-control study in a Chinese population - Xiao Xia Li; Jian Ping Liu; Jin Quan Cheng; Sheng Hong Han; Yi Jie Geng; Sheng Wei; Shi Tong Gao; Da Na Huang; Shao Fa Nie (Molecular Biology Reports, 2009)

Evolution of the Chloroplast trnL-trnF Region in the Gymnosperm Lineages Taxaceae and Cephalotaxaceae - Da Cheng Hao; Bei Li Huang; Shi Lin Chen; Jun Mu (Biochemical Genetics, 2009)

Hyper-spectral remote sensing to monitor vegetation stress - Hong-Yan Ren; Da-Fang Zhuang; Jian-Jun Pan; Xue-Zheng Shi; Hong-Jie Wang (Journal of Soils and Sediments, 2008)

Comparative Physicochemical Characterization of Phospholipids Complex of Puerarin Formulated by Conventional and Supercritical Methods - Ying Li; Da-Jian Yang; Shi-Lin Chen; Si-Bao Chen; Albert Sun-Chi Chan (Pharmaceutical Research, 2008)

Heavy metals in bark of Pinus massoniana (Lamb.) as an indicator of atmospheric deposition near a smeltery at Qujiang, China - Yuan Wen Kuang; Guo Yi Zhou; Da Zhi Wen; Shi Zhong Liu (Environmental Science and Pollution Research, 2007)

Study progress in therapeutic effects of traditional Chinese medicine monomer in severe acute pancreatitis - Xi-ping Zhang; Da-ren Liu; Yan Shi (Journal of Zhejiang University-SCIENCE B, 2007)

A novel bieremophilanolide from Ligularia lapathifolia - Yun-Sen Li; Shao-Shun Li; Zheng-Tao Wang; Shi-De Luo; Da-Yuan Zhu (Natural Product Research, 2006)

Sensitized photooxidation of furanoeremophilane with singlet oxygen and their biogenetic relationship - Yun-Sen Li; Zheng-Tao Wang; Shi-De Luo; Shao-Shun Li; Da-Yuan Zhu (Natural Product Research, 2006)

Characterization of on-road CO, HC and NO emissions for petrol vehicle fleet in China city - Hui Guo; Qing-yu Zhang; Yao Shi; Da-hui Wang; Shu-ying Ding; Sha-sha Yan (Journal of Zhejiang University-SCIENCE B, 2006)

The style–length of the female florets and their fate in two dioecious species of Xishuangbanna, China - Zhang-Hong Shi; Da-Rong Yang; Yan-Qiong Peng (Trees, 2006)

Study on US/O3 mechanism in p-chlorophenol decomposition - Xian-wen Xu; Xin-hua Xu; Hui-xiang Shi; Da-hui Wang (Journal of Zhejiang University-SCIENCE B, 2005)

Ozonation with ultrasonic enhancement of p-nitrophenol wastewater - Xian-wen Xu; Hui-xiang Shi; Da-hui Wang (Journal of Zhejiang University-SCIENCE B, 2005)

Role of tumor metastasis suppressor gene KAI1 in digestive tract carcinomas and cancer cells - Qiao Wu; Yuan Ji; Ming-qing Zhang; Yu-qiang Chen; Fu Chen; Da-lin Shi; Zong-hui Zheng; Yao-jian Huang; Wen-jin Su (Cell and Tissue Research, 2003)

Toxicity of Bacillus sphaericus LP1-G Against Susceptible and Resistant Culex quinquefasciatus and the Cloning of the Mosquitocidal Toxin Gene - Yong-Xia Shi; Da-Sheng Zheng; Zhi-Ming Yuan (Current Microbiology, 2003)

Rapid decrease of RNA level of a novel mouse mitochondria solute carrier protein (Mscp) gene at 4–5 weeks of age - Quan-Zhen Li; Sarah Eckenrode; Qing-Guo Ruan; Cong-Yi Wang; Jing-Da Shi; Richard A. McIndoe; Jin-Xiong She (Mammalian Genome, 2001)

Fresh snow chemistry from high mountain regions in central himalayas - Shi-chang Kang; Da-he Qin; Tan-dong Yao; A. Mayewski Paul; Whitlow Sallie (Chinese Geographical Science, 2000)

Characterization of mutations in patients with autoimmune polyglandular syndrome type 1 (APS1) - Cong-Yi Wang; Abdoreza Davoodi-Semiromi; W. Huang; Ellen Connor; Jing-Da Shi; J.-X. She (Human Genetics, 1998)